GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 947559373 species occurrences available in GBIF matching the query: Year: 1000-2018. The dataset includes 947559373 records from 15000 constituent datasets: 8 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 1728 records from Collection rousset -1947-2013. 1860 records from Données naturalistes de Hervé BOUYON. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 7 records from Thistle Heads and Ermerged Insects. 143 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 108 records from Total foraminifera counts of multinet M21/2_MSN629. 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 3 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 152 records from Total foraminifera counts of multinet POS247/2_MSN1372. 2 records from Dinoflagellate abundance of Hole 85-572C. 25 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanterriidae).. 766 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 9 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 130 records from ABC_Ndangopuma_hills_eventdata_25_11_2005. 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 4158 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1941 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3078 records from Insectes Hyménoptères Scollidés de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 15 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6190 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 361 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 145 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 4751 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 210 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 470 records from Gewann Krampf (Heilbronn). 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 17 records from Benthic macrofauna abundance of sediment core 13201-002. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 320 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 607 records from Inventory of Bassila forest (North-Benin). 406 records from Pollen profile from Muscotah Marsh B. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 48 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 718 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 120 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 30 records from Planktic foraminifera abundance of Hole 14-144. 8 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 1 records from Hemichordata collection of National Museum of Nature and Science. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 157 records from Planktic foraminifera counts at CTD station PS55/078-1. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 11 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 79 records from Birdrace-Bielefinken-Bielefeld. 107 records from Müritz-Nationalpark. 125 records from Range table from ostracoda in ODP Hole 143-866B. 65 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 913 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 5999 records from Colección Limnológica Universidad de Antioquia. 1 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 272 records from Wald am Schloss Wittgenstein Bad Laasphe. 564 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 176888 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 35 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 2 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 41 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 2 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 746 records from Données naturalistes de François BRETON. 10 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 26225 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 210 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 5264 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 28075 records from Lepidoptera specimen database of Japan. 308173 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 2499 records from Leicestershire and Rutland Reptile Records to 2011. 33 records from Smear slide analysis on sediment core GeoB4214-1. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 1599 records from Culture Collection of Algae. 2419 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 374 records from Planktic foraminifera abundance of Hole 68-503B. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 18243 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 372 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 22 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 265 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2). 592 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 18 records from Schulgarten der Gesamtschule Am Heidberg. 22 records from Coccolith counts of multinet SO119_MSN1272. 2584 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1215 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 480 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 814 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 190 records from Relative abundance of ostracods in sediment core Sv09. 5095 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 181977 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 24 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 48 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 83 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 318 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 4065 records from Estación Biológica de Doñana - CSIC, Anfibios. 28033 records from R. L. McGregor Herbarium Lichen Collection. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 472 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 10173 records from UAM Fish Collection (Arctos). 1070 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 70 records from Isotope tracer experiment: meiofauna counts. 557 records from Corn bunting breeding distribution in Scotland. 2297 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 69 records from Foraminifera species abundances from tow TT007_7-MOC13. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 15 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 32 records from Nannofossil abundance of Hole 94-611E. 127 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 153 records from Selztal bei Friesenheim. 28 records from Microzooplankton abundance and biomass at station TT045_19-3. 17077 records from UCM Mammal Collection (Arctos). 21 records from Riedkanal Bötzingen. 5 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 20 records from Planktic foraminifera abundance of Hole 19-185. 64 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 1029278 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 19020 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2154 records from DBG Physaria bellii Demographic Monitoring. 11 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 20 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 15 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 19 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 193 records from Planktic foraminifera abundance of Hole 94-610. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 62319 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 69 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 5 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 9 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 264 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 44 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 480819 records from KTP Ring Data. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 10 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 16442 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 588 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 23 records from Morphologische Daten von Natrix. 18 records from Collection botanique Lamy de la Chapelle E. (BOUM). 1703 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 4726 records from LISU Herbario Angola. 3847 records from CNAC/Coleccion Nacional de Acaros. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 466 records from Nannofossil abundance of Hole 4-31. 622 records from hauterivian_echinoids_of_the_paris_basin. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 2 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 115 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 1824 records from TransForest vegetation data. 247 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 201 records from Biodiversity of springs and rock seepages 2003. 127 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 68 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 1 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 1 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 2205 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 6368 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 75 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 234 records from Données Phesulma borbonica du Parc national de La Réunion - COBE03. 93 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 909 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 444 records from Marsabit Ecosystem Inventory Surveys 2014. 4 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 21 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 1052 records from Nannofossil abundance of Hole 37-334. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 2 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 59 records from Schulgelände SGD/Viersen. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1303 records from Flora genérica de las gramíneas del estado de Tlaxcala. 1 records from Zur Kenntnis der Lithobiiden. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 322 records from Nannofossil abundance of Hole 84-570. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 1341 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 53 records from Leopard and Weddell seal program 1999/2002. 4309 records from Données naturalistes de Ségolène FAUSTEN. 62 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 2 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 7339 records from Natural History Museum Maastricht (NL) - Herbarium. 172 records from Foraminifera abundance of sediment core MD81-LC07. 7 records from Invertebrate collections. 403 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 16248 records from Collection of Coleoptera. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 1 records from Karpfenteich, Klasse 6d. 6 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 59 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 179 records from Total foraminifera counts of multinet SO117_MSN1244. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 7 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 687036 records from Queensland Museum provider for OZCAM. 71 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379. 192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 70 records from Coccoliths in sediment core GIK23065-3. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 121 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 96 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 107 records from Range table from benthic foraminifers in ODP Hole 146-889B. 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 701 records from Données naturalistes d'Arnaud LE NEVÉ. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 12 records from Analyses of the recent components of sediment core PS1219-1. 717 records from Redland City Council Citizen Science Portal. 42696 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 4 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 239 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 339 records from HBRG Invasive Non-native Plants Dataset. 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1654 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 806 records from Pollen profile V and Ausfluss at Krumbach, Germany. 569 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 183430 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 20725 records from Birds Specimens. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 86 records from Fliegenhaupt Marksuhl. 56 records from Planktic foraminifera abundance of Hole 23-227. 80 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 18804 records from DMNS Mammal Collection (Arctos). 2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 226 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 2281 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 2 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 881 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 79 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 1052 records from IBF Monitoring of Fungi. 2242 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 4 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 883 records from Nannofossil abundance of Hole 15-154A. 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 119 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 10170 records from Données de la collection d'ichtyologie du MNHN (GICIM). 66 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 53 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 240 records from Knechtweide (Kohlfurth). 18 records from Benthic macrofauna abundance of sediment core 12930-073. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 89 records from Meniscus Midges (Dixidae) of Ireland. 68 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 1 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 224 records from Natura 2000 PnrL. 11028 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 2 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 830 records from Zambian Bat Collections Worldwide. 7 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 458 records from PSU-Seagrass Collection. 336 records from Entomological collection of the National Museum. 30915 records from Vascular plants of south-central China. 206 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 144 records from BIRDRACE Punkbirder Helgoland. 1 records from Miriapodi di alcune grotte della Campania. 554 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 53 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 318 records from Nannofossil abundance of Hole 4-29. 2071 records from Helmintos parásitos de peces del sureste de México. 61 records from Naturpark Kottenforst-Ville 15.6.09. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 3 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 418 records from Radiolaria assemblage in sediment core GIK23259-2. 268 records from Range table from benthic foraminifers in ODP Hole 159-959A. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 173 records from FFH-Gebiet Klosterwasser/Burkau. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 197501 records from Natural History Museum, Vienna - Herbarium W. 36 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 2697 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 2255 records from (Appendix B) Benthic foraminifera extinction group species in combined DSDP Hole 33-317B and sediment core KR9912-PC4. 34 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 66 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 1748 records from Floral visits on plants, InsectScale 2008. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 3 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 30 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 5 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 1 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 1436 records from Stoneworts in Wales. 1900 records from Fungi Collection. 6 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 11 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 32694 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 180 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 120 records from Total foraminifera counts of multinet M10/2_MSN262. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 2174 records from ConDidact Citizen Science Surveys - Snails 2006. 363 records from Range table from planktonic foraminifers in ODP Hole 182-1129C. 23 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 282 records from Deponie Klausdorf. 47 records from Schulgelände (Wetter). 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 6 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 3093 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 61 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 14387 records from Enquête Lucane. 5422 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 961 records from Erlengraben/Lipp-Tal (Östringen). 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 4 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 31 records from Benthic foraminifera abundance of Hole 42-379A. 392 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1806 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 19 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 2508 records from BioGIS - Reptiles - HUJ collections. 19 records from Microplankton data off Mejillones, 2006, Chile. 10 records from Analyses of the recent components of sediment core PS1222-1. 49 records from Coccoliths in sediment core PS1535-8. 648460 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5428 records from Fishes in the Argentine Sea from 1967 to the present time. 7 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 82 records from Dpto. de Botánica, Ecología y Fisiología Vegetal (Histórico COFC). Facultad de Ciencias. Universidad de Córdoba. 232 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 4 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 139 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 899 records from Stable isotopes and content of foraminifera at Hole 130-805C. 529 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 1169 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 10 records from Ostracoda abundance of Hole 32-306. 875 records from Nannofossil abundance of Hole 29-281. 26 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 59680 records from Butterflies of Ireland. 315 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 13 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 580 records from Rare plants database extract from Scottish Natural Heritage. 68396 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27160 records from Formidabel; Belgian Ants Database. 493 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 194 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 1148 records from ABC event data for Nyika Plateau, Buma Hills. 126 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 1 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 151111 records from CAS Invertebrate Zoology (IZ). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5978 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 817 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 109 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 1270 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 9482 records from NSW South Coast & ACT plants. 148 records from Abundance of birds in the Lena Delta Region. 81 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 29 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 324 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 2 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 19 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 178 records from (Table 9) Relative abundance of benthic foraminifera in ODP Hole 112-685A. 2 records from Deep-sea ascidians from Papua New Guinea. 59 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 172 records from Total foraminifera counts from multinet M31/3_MSN915. 987512 records from NatureServe Network Species Occurrence Data. 41676 records from Tagged Seal Location Data from SOGLOBEC. 333 records from Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 2619 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 836 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1709 records from The Gibson spider collection. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 15 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 7 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 1256 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 651 records from Réseaux écologiques/Trame verte et bleue. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 7 records from Content of G. menardii in sediment core V25-70. 66164 records from Florida Keys Reef Visual Census 1996. 7950 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 783 records from Neogene palynomorpha from site 93-603, part 2. 5 records from Society Islands beach bum black flies (Diptera: Simuliidae). 965 records from Nannofossil abundance of Hole 75-532. 62 records from Données de Mammifères marins en Polynésie française issues du South Pacific Whale Research Consortium. 15 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 2725 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 515 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 81329 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 9143 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 6776 records from Hormigas del Museo de Entomología de la Universidad del Valle. 13 records from Reptiles Specimens of Akita Prefectural Museum. 205 records from UWIZM Snakes. 113 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 10552 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 364 records from Nannofossil abundance of Hole 85-573. 8 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113. 141 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 168 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 33 records from Microzooplankton abundance and biomass at station TT043_27-1. 11086 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 7718 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 176 records from Renaturierung Werse (Innenbereich Beckum). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 52755 records from FUEL - Herbário da Universidade Estadual de Londrina. 280 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 11454 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 96 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 20191 records from Seabirds in Norway - Estimated population sizes. 80 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 444 records from South Lanarkshire peatland records 2013. 12 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 1032 records from Étude entomologique des forêts publiques de Martinique, pour l'ONF. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 276 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 44 records from Planktic foraminifera abundance of Hole 63-472. 2704 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1649 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 675 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 71862 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15360 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 4 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 345 records from (Table 3) Relative abundance of selected benthic foraminifera in ODP Hole 104-642C. 560 records from Planktic foraminifera abundance of Hole 15-149. 3939 records from Census of plant species in Pahou forest reserve. 141 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 31 records from Lepidurus arcticus survey Northeast Greenland 2013. 153 records from VSN-Wiese. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 10 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 7388 records from Ibaraki Nature Museum, Fungi collection. 14 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 24387 records from Données de Luc BARBARO. 34 records from Planktic foraminifera counts of sediment core ELT48.011-PC. 212 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 756 records from Mokihinui and Karamaea small tributaries and seeps. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 829 records from If_Ecologie_Conseil_2017_12_18. 227 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 19 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 1254 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 915 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 48 records from Total foraminifera counts of multinet M6/7_MSN140. 1476 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 9143 records from Royal British Columbia Museum Entomology Collection. 129 records from Dinoflagellate abundance of Hole 81-552. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 421 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 2 records from The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia. 280 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 551 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8409 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3001 records from Colección Entomológica CDMB. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 196 records from (Fig. 10) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 41-367 in the North Atlantic. 16931 records from Lepidoptera (Specimens NRM). 250 records from Colección nacional de palmas de Colombia - JBQ. 993 records from ROC RSPB Farmland Species Survey Dataset. 3269 records from Relative abundance of radiolaria in surface sediments. 205 records from Wild boar sightings held by Andy Riches. 1644 records from Las comunidades de myxomicetes de selva baja caducifolia. 182049 records from Florida Keys Reef Visual Census 1999. 108 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 27728 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 22534 records from Tachinid Recording Scheme - GB and Ireland records. 241 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 4617 records from Données de type contact de Guadeloupe. 1729 records from Canadian Museum of Nature Palynology Collection. 97 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 261 records from Planktic foraminifera abundance of Hole 63-469. 1284 records from Données naturalistes de Thomas LORICH. 408 records from Planktic foraminifera abundance of Hole 23-220. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 36 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 96 records from Range table from benthic foraminifers in ODP Hole 172-1060B. 55 records from Galls on Beech Trees in Hainich, 2008. 2039 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 154 records from Range table from planktonic foraminifers in ODP Hole 170-1041A. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 659 records from (Table 1) Pleistocene planktonic foraminiferal assemblages at ODP Site 128-798. 31788 records from Observatoire de la Biodiversité des Jardins (OBJ). 129 records from Plasm bearing foraminifera counts of multinet M21/2_MSN657. 469 records from Nannofossil abundance of Hole 10-94. 118 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 1 records from Ctenophora ZMK. 182 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 2290 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 1 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 79 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 6263 records from Range table from nannofossils in ODP Hole 164-994C. 648 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 535 records from Pollen analysis of sediment core GeoB6518-1. 5 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 494248 records from BLS Mapping Scheme dataset, 1750-2009. 11 records from Description of lithologic section units of IODP Hole 325-M0055A. 244 records from Quarrendorfer Landschaftsschutzgebiet. 162 records from Registros de quirópteros de tres localidades del caribe colombiano. 24 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 7 records from Range table from benthic foraminifers in ODP Hole 139-856C. 5 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 324 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 14 records from BMHS Crustacean Collection. 29 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 37 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 2183 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 1 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 239 records from Données naturalistes de Pauline BALDUCCI. 1 records from Planktic foraminifera abundance of Hole 54-420A. 838 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 10698 records from Yoann_BLANCHON_2017_12_18. 2 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 3 records from MSB Mammal Observations (Arctos). 305 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 61718 records from Données "faune" hors insectes pour le SINP île de France. 10 records from Données naturalistes de Sophie COHEN. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 55 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 4 records from New and poorly known Meligethes Stephens from China, with bionomical data on some species (Coleoptera: Nitidulidae: Meligethinae). 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 2876 records from Wikiplantbase #Sicilia. 48 records from Foraminifera and stable isotopes of sediment core PS2076-1. 498 records from Bekkelag basin, Inner Oslofjord. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 29 records from Abundance of benthos infauna at station POS128/2_284. 528 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 648 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 62 records from Benthic foraminifera abundance of Hole 42-380. 1142431 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 54 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 27988 records from Bird records for Argyll for the years 2002 and 2003. 96 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 981 records from Ibaraki Nature Museum, Fish collection. 57 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 13 records from Range table from planktonic foraminifers in ODP Hole 182-1128D. 128 records from Fiocruz/CCAMP - Coleção de Campylobacter. 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 91 records from CNIN/Tipos Homoptera. 328 records from Otter (Lutra lutra), Outer Hebrides. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 39 records from Planktic foraminifera counts of sediment core V19-21. 8 records from The Odonata of Sulawesi and adjacent islands. Part 8. Revision of the genus Rhinocypha Rambur, 1842 (Chlorocyphidae). 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 505 records from National Frog Survey of Ireland 2010/2011. 5244 records from Colección Ornitológica de la Universidad del Valle. 1 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 207 records from Données de Mammifères marins. Mission AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 50381 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 3 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 6 records from Nannofossil abundance of Hole 9-79A. 66 records from Range table from ostracoda in ODP Hole 151-910D. 874 records from The Living Murray Fish data. 23 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 2148 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 25974 records from Long-term Bird Census in Cigu 2004-2017. 124 records from Nannofossil abundance of Hole 24-233. 1426 records from CNIN/Tipos Coleoptera. 4 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 1128 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 213 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 246 records from BARTH-Environnement_2017_12_18. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 22 records from Additional new species of the genus Obolopteryx Cohn et al. 2014 (Ensifera: Tettigoniidae) from Northeastern Mexico. 92 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 5277 records from SANBI: DNA Banking(1987-2011). 162 records from Total foraminifera counts of multinet M21/2_MSN658. 933 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 20381 records from Naturalis Biodiversity Center (NL) - Mammalia. 25 records from Microzooplankton abundance and biomass at station TT043_11-1. 621 records from Nannofossil abundance of Hole 74-525A. 4 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 101 records from BIRDRACE Enger am Spektiv. 1784 records from Ghent university - Zoology Museum - Nematod Collection. 131 records from Total foraminifera counts from multinet M32/3_MSN956. 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 3 records from Taxonomic changes in Salyavatinae (Heteroptera: Reduviidae), with an updated generic key. 6170 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 80 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 518 records from Nannofossil abundance of Hole 49-410. 3304 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 322193 records from Florida Keys Reef Visual Census 2010. 21278 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 10 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 153 records from annex1. 132 records from Total foraminifera counts of multinet POS247/2_MSN1377. 2365 records from Sutton Hoo species data held by The National Trust. 39 records from Dinoflagellate abundance of Hole 28-270. 39 records from Nannofossil abundance of Hole 66-493A. 4 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 3276 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 200 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 141 records from Draubiotop Lavamünd. 2 records from Netzfluegler_Raw1. 115 records from Foraminifera species abundances from tow TT011_12-MOC74. 55 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 114 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 8197 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 92 records from Birdrace_TerraCamper-Münster. 4 records from Revised status of Oridryas Meyrick, 1938: new synonyms of Ypsolopha Latreille, 1796, and Ypsolopha parenthesella (Linnaeus, 1761) (Yponomeutoidea: Ypsolophidae). 293 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 15 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 5 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 2852 records from AlgaTerra. 1315 records from Records from the South Australian Seed Conservation Centre. 117 records from Distribution of planktonic foraminifera of sediment core SH1972_7. 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 33 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 38 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 34 records from Borkhart. 7114 records from HSU Vertebrate Museum Mammals Collection. 8160 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 226 records from Planktic foraminifera assemblage in sediment core GIK17730-4. 3459 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 39 records from Nannofossil abundance of Hole 9-80. 4 records from Two new species of Miltochrista from India (Lepidoptera, Erebidae, Arctiinae). 128 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 348 records from Foraminifera abundance of Hole 57-440B. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 4 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 239 records from Rutilans. 516 records from UTEP Insects (Arctos). 15283 records from Leicestershire Bryophyte Data. 10 records from Données naturalistes de DURON Cyril. 19722 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Endemic Families of Madagascar. XIV. a New Restricted Range Species of Pentachlaena H. Perrier (Sarcolaenaceae) from Central Madagascar. 901 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 59 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 346 records from Packer Collection /Madagascar. 13 records from Rediscovery and redescription of Laelaps lignicola G. & R. Canestrini, a remarkable myrmecophilous mite of the genus Cosmolaelaps Berlese (Acari: Mesostigmata: Laelapidae) from Italy. 9 records from Distribution of meiobenthos in sediment core M19_202-2 of the northeastern Atlantic (Table 1). 19 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 188 records from Planktic foraminifera distribution of sediment core GIK17940-2. 27 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 523 records from Anfibios de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 94 records from Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb.. 3641 records from Fish: Records for Kent.. 39 records from Nannofossil abundance of Hole 39-353. 1 records from Planktic foraminifera abundance of Hole 54-428. 519 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 2 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 14 records from Benthic macrofauna abundance of sediment core 13200-045. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 15 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 1 records from On the Chilopoda from Turkey. 2284 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 271 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 160215 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 28 records from Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 2411 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 28 records from Halophila stipulacea in the Caribbean Sea. 1 records from Annotated catalogue of the click-beetle subfamily Tetralobinae (Coleoptera: Elateridae). 21 records from Taxonomic revision of the flavopalliata species group of Signiphora (Hymenoptera: Signiphoridae). 2167 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 492 records from Phytoplankton abundance off Chao island in Juli 2003, Peru. 468 records from Données naturalistes de Bastien TRAN. 5 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 509 records from Nannofossil abundance of Hole 94-606A. 40135 records from DIBA-Parc del Montnegre i el Corredor. 4761 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 223 records from Planktic foraminifera abundance of Hole 40-362A. 5 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 21456 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 2 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 7 records from Grundwasserlebensraum im Englischen Garten (München). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 52 records from Range table from planktonic foraminifers in ODP Hole 167-1010E. 5 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 8266 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 96 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 2939 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 31613 records from MCP - Coleção de Abelhas. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 26 records from Erhard Sopp. 67 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 134 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 180 records from Données naturalistes de Pascal Dupont. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 1 records from Aglaotilla, a new genus of Australian Mutillidae (Hymenoptera) with metallic coloration. 238 records from Bird specimens of Bihoro Museum. 239 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 876 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 2 records from Wie viel Natur gibt es im Park?. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 612 records from HerpMapper. 985 records from Freshwater Fishes of Bulgaria. 403 records from Nannofossil abundance of Hole 4-25. 10111 records from NBMB Herps. 386 records from Foraminifera distribution of sediment core KS310. 434 records from Aves de Caño Cristales, La Macarena, Meta. 5979 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 310 records from Umgebung der Gesamtschule Hamburg-Winterhude. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 1577 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 170 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 3189 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 1247 records from Revues diverses et littérature grise.. 69 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 114 records from (Table 4) Thecosomata in ODP Hole 134-831A. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 22 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 1818 records from Distribution of planktic foraminifera of sediment core M33/1_SL_NAST. 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 59 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 3 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 770 records from Distribution of major planktic foraminifer at Site 177-1093. 565 records from Expedición Providencia I - INVEMAR. 7 records from Description of lithologic section units of IODP Hole 325-M0050A. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 50 records from Lindesnes. 10 records from Planktic foraminifera abundance of Hole 15-154A. 203712 records from University of Michigan Museum of Zoology, Division of Birds. 404 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 5 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 1921 records from Foraminifera abundance of Hole 61-462. 640 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 254 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1836 records from Phytoplankton abundance in surface water in October 1996, Ilo, Peru. 5897 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 242 records from UTEP Fish (Arctos). 14 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 50 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 4 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 60951 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 3740 records from (Table S2a) Nannofossil species richness in the Bass River section. 2 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 4031 records from Benthic foraminifera distribution of sediment core GIK17957-2. 10 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 15691 records from Mollusques dulcicoles de France - Jacques MOUTHON. 606 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 610 records from BID-Malawi-Geometridae-Biodiversity-Data. 3 records from A new species of the Liolaemus alticolor - bibronii group (Iguania: Liolaemidae) from East-central Argentina. 360 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 32 records from Foraminifera species abundances from tow TT007_15-MOC23. 164 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 49923 records from Collection Aves (bird skins) SMF. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 4054 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 46 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 13820 records from JOI - Herbário Joinvillea. 2 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 3 records from Microplankton counts and carbon biomass at station TT007_9-CTD108. 65 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 84 records from BIRDRACE Vogelscheuchen. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 314 records from Planktic foraminifera abundance of Hole 21-207A. 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 3760 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 80649 records from NINA Vanndata fisk. 510 records from Inventaires des cygnes du département de l'Eure. 3 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 96 records from Peces de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 61 records from Artenvielfalt in der Kinderakademie im RFZ. 23 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 2018 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 1399 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 53062 records from British Antarctic Survey Argos satellite tracking data. 1272 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 260 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 47 records from A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species. 754 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 114 records from Total foraminifera counts of multinet M26/1_MSN844. 600 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 31 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 48 records from Freiheitsring (Frechen). 3 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 3461 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 2 records from Erythrodiplax ana sp. nov. (Odonata: Libellulidae) from Brazilian palm swamps. 6992 records from Stone-curlew Annual Surveys. 29646 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 1138 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 2 records from Taxonomic review of the genus Wasmannia.. 1363 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 192 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 12761 records from Données naturalistes de Franck NOEL. 343 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 2 records from A new species of Oncopeltus Stål, 1868 (Heteroptera: Lygaeidae) in the nominate subgenus from Ecuador. 265 records from Luderbusch. 1849 records from Heigham Holmes species data held by The National Trust. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 2499 records from Collections data on ecology of bottom animal of the Southern ocean. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 5 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 1363 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 170 records from Planktic foraminifera abundance of Hole 94-610B. 244 records from Malawi-Cicindelidae-Biodiversity-Data. 17732 records from Fish Collection of Yokosuka City Museum. 3 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 29 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 12 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 1988 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 26897 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 5 records from Schulinnenhöfe (Gelsenkirchen). 160 records from Wirbach-Taubental (Bad Blankenburg). 9 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 6 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 286 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 15 records from Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae). 17135 records from Insect specimens of Himeji City Science Museum. 3477 records from (Table 13) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-591. 3 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 26 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 145 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 4812 records from Fish specimens of Natural History Museum, Kishiwada City. 5965 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 15 records from New species of the genus Gnathochorisis Förster (Hymenoptera: Ichneumonidae: Orthocentrinae) from the Neotropical Region. 1594 records from Abundance of algae in the Aral Sea. 27889 records from Lizard Island Research Station. 29 records from Naturerfahrung. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 2127 records from ISM Herpetology Collection. 203 records from Total foraminifera counts from M35/1_MSN1047. 80572 records from Steiermärkisches Landesmuseum Joanneum - Herbarium GJO. 20 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-14-13. 4050 records from Range table from benthic foraminifers in ODP Hole 159-962D. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 15293 records from UAZ Bird Collection. 19 records from Suivi des reptiles des landes du Technopôle du Madrillet. 138 records from Total foraminifera counts of multinet M12/3_MSN535. 896 records from Data on agroforestry plant species of Benin. 1266 records from Insectes Hyménoptères Formicidés de Corse. 740 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 3460 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 1 records from V ° Contributo alla conoscenza dei miriapodi cavernicoli italiani. 141 records from Total foraminifera counts from multinet M31/2_MSN888. 5 records from A new species of Olecryptotendipes Zorina from China (Diptera, Chironomidae). 17 records from Benthic macrofauna abundance of sediment core 13078-013. 1075 records from Planktic foraminifera counts of sediment core RC14-35. 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 420 records from Relative abundance of ostracods in sediment core St09. 30 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 25 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 166 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 240 records from (Table 4) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-681A. 21 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 315 records from Range table from planktonic foraminifers in ODP Hole 155-945A. 3066 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 574 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 238 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 8 records from Phoronida - SMF. 383 records from Pollen counts of sediment core GeoB9503-5. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 331 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 18 records from Microplankton counts and carbon biomass at station TT008_5-CTD25. 410 records from Planktic foraminifera abundance of Hole 22-216. 97 records from Landschaftspark St.Leonhard-Deisendorf. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 24 records from Abundance of coccosphere-units of sediment core GIK23071-3. 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 522195 records from Parc_National_de_Port_Cros_2017_12_18. 2000 records from Diversidad y distribución de los copépodos (Cyclopoida) de las zonas áridas del Centro-Norte de México. 12 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 94882 records from MPM Milwaukee Public Museum Herbarium. 6 records from New synonymy, new species, new keys to Neivamyrmex army ants of the United States.. 57 records from Trimma tevegae and T. caudomaculatum revisited and redescribed (Acanthopterygii, Gobiidae), with descriptions of three new similar species from the western Pacific. 34 records from Range table from planktonic foraminifers in ODP Hole 173-1068A. 85 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 21 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 9 records from Analyses of the recent components in the sand fraction of sediment core PS1216-1. 54 records from Review of the leafhopper genus Anufrievia Dworakowska (Hemiptera: Cicadellidae: Typhlocybinae: Erythroneurini). 630 records from Report on the Danish Oceanographical expeditions 1908-1910 to the Mediterranean and adjacent seas - PelagicPolychaetes. 20144 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 422 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 909 records from Dinámica poblacional de la tortuga de carey (Eretmochelys imbricata) en su área de forraje. Río Lagartos, Yucatán. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 143 records from Range table from planktonic foraminifers in ODP Hole 160-966F. 117078 records from KUBI Ornithology Collection. 86 records from Données naturalistes de Françoise SERRE-COLLET. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 4628 records from Distribution of planktic foraminifers of core V30-40. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 33 records from Foraminifera abundance of Hole 55-430B. 2217 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 5028 records from Herbario de la Universidad de Sevilla, SEV-Historico. 11 records from ALP-PAGES_2017_12_18. 4258 records from Colección Herpetológica (anfibios) de la Universidad Industrial de Santander. 1992 records from Actualización de la base de datos de la Colección Regional Durango (Mammalia). 88 records from "Schlechteberg" Ebersbach/Sa.. 15 records from Contribution to the knowledge of Cloeodes Traver 1938 (Ephemeroptera, Baetidae). 7462 records from Colección de Herpetología del Instituto de Ciencias Naturales (ICN-MHN-Her). 936 records from Collection des données de biodiversité marine de Polynésie française. 4484 records from (Table 1) Occurrence of selected planktonic foraminifers, other microfossils, and lithologic components at DSDP Hole 96-619. 2 records from Scirtothrips genus-group in Iran with an unusual new species of Scirtothrips (Thysanoptera: Thripidae). 1 records from Anophtalmic and epigean? Description of an intriguing new species of Hyalella (Amphipoda, Hyalellidae) from Brazil. 180 records from (Table 2) Eocene benthic foraminiferal community of DSDP Holes 95-613 and 11-108. 2 records from Three new species of Synagelides Strand, 1906 from China (Araneae: Salticidae). 109 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1172D. 136 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1371. 74 records from Nannofossil abundance of Hole 1-3. 5 records from (Table 7) Paleotemperature estimates for ODP Hole 104-642B. 611 records from Planktic foraminifera counts of sediment core V29-64. 27 records from Schulgarten Waldorfschule Hassfurt. 24013 records from Staatliches Museum für Naturkunde Stuttgart, Herbarium. 135 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - Birdrace-Pody&Co.-Plön. 193 records from Loup 2009 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 11253 records from (Appendix II) Planktonic foraminiferal biostratigraphy of ODP Site 113-690. 2427 records from Base de datos y colección de distintos grupos del zooplancton de regiones marinas prioritarias de Jalisco y Colima en el Pacífico mexicano. 4050 records from Locations of seals in Patagonian Large Marine Ecosystem (OBIS South America, AR-OBIS, Sub-node). 2 records from A new deep-sea Cirripedia of the genus Heteralepas from the northeastern Atlantic. 1 records from Arthropoden aus südostalpinen Höhlen.. 230 records from Phytoplankton abundance during Arne Tiselius cruise AT91/2. 5892 records from Inventario de los ropaloceros (Lepidoptera) de la Sierra Gorda, estado de Querétaro, México. 1 records from Altigena malihkaia, a new species of Labeonini (Teleostei: Cyprinidae) from the Irrawaddy River basin in Myanmar. 9 records from Content of coarse fraction and G. menardii in sediment corev V25-65. 10 records from New species and new records of Uropodina from Virginia, USA (Acari: Mesostigmata). 65 records from A new species of habitat – forming Suberites (Porifera, Demospongiae, Suberitida) in the Benguela upwelling region (South Africa). 1255 records from Plant specimens of the Museum of Yamagata University. 69 records from Nannofossil abundance of Hole 10-86. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 76 records from (Table 1) Counts and concentrations of pollen, spores and dinoflagellate cysts in sediment core MD01-2378. 34 records from Collection Graptolithina fossil SMF. 850 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 81892 records from Specimen Database of Colorado Vascular Plants. 25953 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 79 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 20 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 62 records from Zoo Frankfurt. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 177 records from Canada_BasinMegabenthos2002. 1085628 records from Fungal Records Database of Britain and Ireland. 150 records from Total foraminifera counts of multinet M21/2_MSN643. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 33 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 752 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61374 records from La familia Asteraceae en México. Fase VI. 630 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 825 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 1594 records from Mycological collection of the National Museum. 1 records from Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran. 63 records from Marine gastropod distribution from patagonian shallow waters. 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 3 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 185 records from Range table from benthic foraminifers in ODP Hole 174-1073A. 55 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 9 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 10004 records from DASSH Data Archive Centre volunteer survey data. 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 121 records from Range table from planktonic foraminifers in ODP Hole 177-1088C. 121 records from BIRDRACE Immerwiederhopf. 8 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 9 records from Plasm bearing foraminifera counts from multinet M31/2_MSN890. 16 records from Dinoflagellate cysts of surface sediments. 7 records from Collection Malakologie - SMNG. 47 records from Données d'observation de phanérogames marines en Martinique. 439 records from Antarctic and Subantarctic Asteroid zoogeography. 4 records from New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae). 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 374 records from Coastal and Marine Species Database. 229 records from Nannofossil abundance of Hole 67-499. 100 records from Data from vegetation plots at Atiquipa, Southern Peru. 54 records from Weidegebiete in der Selzrenaturierung. 45 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 744 records from Ostracoda in sediment core PS51/159-10. 2 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 2 records from Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae). 3 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 834588 records from Liste des espèces de la faune sauvage (Amphibiens, Mammifères hors Chiroptères, Oiseaux, Orthoptères, Reptiles & Rhopalocères) observées selon le maillage communal français de la base de données naturalistes Faune-France .. 579 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 78 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 5 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 262 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 316 records from Planktic foraminifera abundance of Hole 42-375. 2223 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 17807 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 96 records from Planktic foraminifera abundance of Hole 32-305. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 18 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 18224 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 1514 records from Gemeinde Sursee. 277 records from Nannofossil abundance of Hole 67-496. 5217 records from Insect specimens of Omogo Mountain Museum. 537 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 852 records from OMMAG_Suivi_Dauphins_Les_Saintes. 508 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 1375 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 3 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 33 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 199 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 106 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 76 records from Inventario de Mamíferos Mámbita. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 55729 records from Canadian Museum of Nature Mammal Collection. 205 records from Pollen and spore abundance of Hole 42-381. 189 records from Naturpark Sternberger Seenland. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 266516 records from Biodiversitätsdatenbank des Landes Salzburg. 12 records from Les occurrences des Gymnospermes de l'herbier du Centre National de Floristique (Côte d'Ivoire). 97 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 4312 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 459 records from DMNS Parasite Collection (Arctos). 204 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 4 records from A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group. 1 records from Predatory Dinosaurs of the World. 19 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 3 records from Dinoflagellate abundance of Hole 14-136. 3294 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 941 records from Nannofossil abundance of Hole 64-476. 1627 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 16623 records from Colección general del plantas vasculares del Herbario JBB. 2188 records from Données naturalistes de Matthias COLIN. 35 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 1568 records from Cowan Tetrapod Collection - Herpetology. 170 records from Total foraminifera counts from multinet M31/3_MSN898. 241 records from (Table 1) Distribution of benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 12-119 in the Bay of Biscay. 565856 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 72 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 12454 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 600 records from Upper Silesian Museum, Bird Collection. 197 records from Phytoplankton abundance at station CD46_0705C#4. 258 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/049-3. 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 2 records from A review of the genus Syrianarpia Leraut (Crambidae: Scopariinae) with description of S. elburzalis sp. n. from Iran. 29 records from Hemmerder Schelk (Unna). 11 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 1 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 4 records from Muséum de Nîmes. 2304 records from Ridge to Reef Marine Monitoring of Fanga'uta Lagoon, Tonga, October 2017. 4314 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 2456 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 13 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 2 records from Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 49 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 277 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 6 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 436 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 1 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 881 records from Moluscos Marinhos de Augusto Nobre. 332 records from Poissons et Crustacés d'eau douce de la Martinique. 89 records from Planktic foraminifera abundance of Hole 63-470A. 6250 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 60 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 157 records from Loup 2009 présence régulière communale (réseau Loup-Lynx ONCFS). 7 records from Boraginaceae (Cynoglossum cherangauiense). 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 38 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 3 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 59 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 735 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 1016 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 353 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 298 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 2084 records from Occurrence data of tree species for crystalline Mountain Forest of Tanzania.. 209 records from Nannofossil abundance of Hole 47-398. 7 records from The millipede family Paradoxosomatidae in the Philippines, with a description of Eustrongylosoma penevi sp.n., and notes on Anoplodesmus anthracinus Pocock, 1895, recorded in Malaysia and Sri Lanka for the first time (Diplopoda, Polydesmida). 626 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 1107 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 16447 records from Capture of Primary Biodiversity Data for West African Plants. 5 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym. 660 records from MVZ Hildebrand Collection (Arctos). 80 records from Foraminifera distribution of sediment core SDSE189. 5 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 21 records from Taxonomy and ecology of a new species of Corynura (Hymenoptera: Halictidae: Augochlorini) from Chile and Argentina. 1477 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 27 records from Planktic foraminifera abundance of Hole 18-174. 87 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 11853 records from California State University, Long Beach Mammals. 80 records from Total foraminifera counts from multinet SO119_MSN1303. 68 records from Revisions of Australian ground-hunting spiders. V. A new lycosoid genus from eastern Australia (Araneae: Tengellidae). 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 5071 records from Données de mammifères enregistrées dans BazNat - Lot 2. 1357 records from Ostracoda in sediment core PS51/154-11. 45 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 83 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 29 records from Waldwiese. 182 records from Planktic foraminifera counts at CTD station M39/4_361CTD-18. 848 records from Nannofossil abundance of Hole 24-231. 3403 records from Clare Biological Records Centre Dataset 2004-2007. 235 records from Expédition Karubenthos 2012 : données issues des publications. 7 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 10 records from A new species of Eidmanacris Chopard, 1956, with notes on its distribution in Brazilian caves (Phalangopsidae, Luzarinae). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 3 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 516 records from Données naturalistes de Laurent KREMMER. 717 records from Biological Collection, National Institute of Oceanography, Goa, India. 1671 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 961 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 150 records from Steinbruch Mainz-Weisenau. 1214 records from Palynological analysis of sediment core GeoB3910-2. 121 records from Total foraminifera counts of multinet M12/3_MSN557. 1518 records from (Table T5) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P9-P11. 3755 records from Fauna y flora del municipio de Lipa, Arauca. 1 records from A new species of Crematogaster from the pinelands of the southeastern United States.. 459 records from Insect specimens of Natural History Museum, Kishiwada City. 50 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 55 records from SNH Invertebrate Site Condition Monitoring 2015: Rinns of Islay SSSI. 20033 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 18 records from Biodiversidad en el valle de Cuatro Ciénegas.. 1 records from Ameisen aus Nossi-Bé, Majunga, Juan de Nova (Madagaskar), den Aldabra-Inseln und Sansibar. Gesammelt von Herrn Dr. A. Voeltzkow aus Berlin.. 113 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 270 records from Plantas de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 248484 records from Atlantic Reference Centre Museum of Canadian Atlantic Organisms - Invertebrates and Fishes Data. 180 records from (Table 7) Distribution of the large, many-chambered Globigerinelloides species in DSDP Hole 79-545. 22 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1370. 3 records from Two new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from Thailand. 1575 records from Larval fish at time series station Helgoland Roads, North Sea, in 2004. 32266 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Verified data. 95 records from Kochertgraben II. 197 records from Plasm bearing foraminifera counts from M35/1_MSN1067. 2 records from A new Paramathes Boursin, 1954 (Lepidoptera, Noctuidae) species from China. 37 records from Content of coarse fraction and G. menardii in sediment corev V16-202. 791 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 5251 records from Abundances indices and biological traits of juvenile salmon sampled in the Nivelle river (France). 1758 records from DBRC Reptile Records 1950 - 2015. 42 records from A synopsis of the genus Dorcasta Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Apomecynini). 1 records from A peculiar new beetle from Brazil associated with a cave habitat (Coleoptera, Carabidae, Clivinini). 16540 records from Inventaire des Mammifères marins de France (métropole et outre-mer). 4 records from Cirolana bambang, a distinctive new species of Cirolana Leach, 1818 (Crustacea: Isopoda: Cirolanidae) from Bitung, Indonesia. 5398 records from Appalachian State University, I. W. Carpenter, Jr. Herbarium. 44 records from Données Racoon sur le territoire de la Guadeloupe. 2 records from A new kukri snake (Colubridae: Oligodon) from Hua Hin District, and the first record of O. deuvei from Thailand. 5 records from Taxonomic notes on the genus Protanilla (Hymenoptera: Formicidae: Leptanillinae) from Taiwan. 7 records from Abundance and carbon biomass of phytoplankton at station TT007_3-CTD30. 5 records from A new genus and some new descriptions of the tribe Aemodogryllini (Orthoptera, Rhaphidophoridae, Aemodogryllinae; Aemodogryllini) from China. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171A. 35 records from Mittelriede Höhe Gliesmarode-Braunschweig. 10 records from Two new genera of pyroglyphid mites, Tuccioglyphus and Marioglyphus, with a key to genera of the World (Acari: Pyroglyphidae). 24556 records from Spermatophyta specimens of Iwate Prefectural Museum. 211 records from Stadt Königs Wusterhausen. 534 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE293. 6 records from Oberservation of birds at station PS14/146 along 49° West. 1744 records from BioGIS - Marine snails - HUJ collections. 111 records from Ökologischer Weinberg (Guntersblum). 11281 records from Molluscus specimens of Toyohashi Museum of Natural History. 47201 records from Anfibios y reptiles de las regiones 30 (Parque Natural Sierra Maderas del Carmen); 31 (Sierra El Burro-Río San Rodrigo); 36 (Sierra La Encantada); y 37 (Sierra El Pino), Coahuila. 2 records from Updated catalogue of Iranian Anthocoridae (Hemiptera: Heteroptera: Cimicomorpha). 575 records from Range table from planktonic foraminifers in ODP Hole 155-941A. 471 records from flower availability 2008 Schorfheide. 47754 records from SEWBReC Beetles (South East Wales). 48 records from Ruhrwiesen bei Neheim-Hüsten. 2058 records from Foraminifera abundance of Hole 17-167. 6 records from Partial redescription of pontoniine shrimps Cuapetes nilandensis (Borradaile, 1915) and Cuapetes seychellensis (Borradaile, 1915) (Decapoda: Palaemonidae: Pontoniinae) with remarks on taxonomic status of Cuapetes Clark, 1919 and Kemponia Bruce, 2004. 293 records from Macrofauna, entomofauna y vegetación vascular de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 11 records from Review of the Paratydeidae (Acari: Prostigmata), with description of three new species. 5 records from New taxa of pygmephoroid mites (Acari: Pygmephoroidea: Pygmephoridae, Neopygmephoridae) phoretic on Enoplotrupes sharpi (Coleoptera: Geotrupidae) from Thailand. 692 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 120 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-14. 87 records from Numbers and dry weights of meiobenthos taxa in surface sediments at Fladen Ground station 1, North Sea (Table 6). 271 records from ABC Matandwe Forest Reserve Vegetation Survey. 50095 records from Fungi of Costa Rica (INBio). 27011 records from RHS lily beetle (Lilioceris lilii) monitoring. 8216 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 48 records from Planktic foraminifera abundance of Hole 25-241. 272 records from Lacewings (Neuroptera) of Ireland. 91356 records from 臺灣兩棲類資源調查與教育宣導推廣計畫 Resources survey and education advocacy to promote for Taiwan amphibian resources. 1576 records from (Appendix B) Nannofossil abundances in DSDP Hole 90-594 from the South Chatham Rise, southeastern New Zealand. 17 records from New lineages of Lebinthini from Australia (Orthoptera: Gryllidae: Eneopterinae). 184 records from Kystfuruskoger 2015. 58 records from Collection Bryozoa - ZMB. 119 records from Faunal assemblage of sediment core TR149-38b. 3327 records from MBML-Mamiferos - Coleção de Mamíferos. 3 records from A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India. 10 records from Planktic foraminifera abundance of Hole 20-202. 19 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2212-6. 10889 records from FBIP:IZIKO-UCT:Historical Survey (1930-1980). 119 records from COA Egg Collection (Arctos). 84 records from An update on the spider genus Hexophthalma (Araneae: Sicariidae) in the Afrotropical region, with descriptions of new species. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 206 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE7. 35 records from Plasm bearing foraminifera counts of multinet M21/5_MSN736. 39 records from Macrohongos en el municipio de Medina, Cundinamarca - Proyecto Colombia Bio. 74112 records from Hymenoptera collection of the Finnish Museum of Natural History. 1842 records from Ecología y genética poblacional de la ballena gris Eschrichtius robustus en la Península de Baja California. 10 records from Benthic macrofauna abundance of sediment core 12930-093. 1084 records from JOIw - Xiloteca Joinvillea. 34 records from Lost and found: the Plecoptera types of Blanchard and Mabille, with further contributions to the stoneflies of Chile. 129 records from Streuobstwiese Kattenhund (Schleswig). 16 records from (Table 4b) Abundances of Globorotalia menardii in sediment core INMD-113BX. 4 records from Black grouse lek survey in Wester Ross and Skye 2009. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 117 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 3 records from A new species and notes on unusual natural history of Cladochaeta Coquillett, 1900 (Diptera: Drosophilidae). 557 records from Planktic foraminifera abundance of Hole 49-407. 54 records from VFD-H: MIttelgebirgsweide. 34 records from The interstitial subsoil fauna of the upper beach level at Sarso Beach, Red Sea (Table 2). 717 records from Planktic foraminifera counts of sediment core V14-81. 33 records from Nannofossil abundance of Hole 3-14. 144 records from Elaboración de la base de datos de la colección de cepas de bacterias fitopatógenas de la Dirección General de Sanidad Vegetal. 526 records from Mammal specimens of Saitama Museum of Natural History. 37 records from Planktic foraminifera abundance of Hole 73-522A. 116772 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 40 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 58 records from Relative abundance of coccolith species in surface sediment samples from the Mid-Atlantic Ridge. 5032 records from Données naturalistes de Loïc SALAUN. 2295 records from Invasive species - Fallopia japonica on river dikes along the river Zeeschelde, Rupel and Durme. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 4 records from New species of Dugdaleiella, gen. nov., Kozloviella, gen. nov., and Pfitzneriella Viette from upper elevation Andes of Ecuador and Peru (Lepidoptera: Hepialidae). 22 records from Planktic foraminifera of sediment core GeoB1407-2. 3916 records from Planktic foraminifera (%) of sediment core MD96-2085. 2 records from A new species of Otothyropsis (Siluriformes: Loricariidae) from the upper Río Paraná basin, Paraguay, with a discussion of the limits between Otothyropsis and Hisonotus. 175 records from Nannofossil abundance of Hole 94-611A. 1113 records from Fig. 4. Simplified macrofossil concentration in sediment core Lz1116. 144 records from Abundance of radiolaria at station LV28-42-1. 5292 records from (Table 2) Calcareous nannofossil abundance in ODP Hole 164-994C sediments. 363 records from Lady Beetle (Coccinellidae) Records Comprising the Checklist of Vermont Species. 2392 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 1 records from Données naturalistes de Louis MERTENS. 58 records from Comunidad íctica de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 5 records from Regenwasserabfangbecken Erlenbach. 4521 records from Institut Mediterrani d'Estudis Avançats: IMEDEA-INSECTA. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-04-1. 8 records from A new family, genus and species of freshwater amphipod Australomicroprotopus megacoxa gen. nov. sp. nov. (Senticaudata, Corophiidea, Microprotopoidea, Australomicroprotopidae fam. nov.) from Australia. 4380 records from UNR Herpetology. 5 records from Three new species of spinicaudatan clam shrimps from Australia, all from gnammas (rock pools). 148 records from Abundance of radiolaria at station UT99-21-2. 21 records from Nannofossil abundance of Hole 52-418. 149 records from Schiller Gymnasium Hof 10b. 494 records from Biologische Station im Kreis Wesel. 1432 records from The Apterygota collection (EA) of the Muséum national d'Histoire naturelle (MNHN - Paris). 9 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 22 records from Bachabschnitt der Nette (Osnabrück). 91655 records from Données photographiques validées de la galerie du forum "Le Monde des Insectes". 358 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 2 records from A new species of Cryptoperla Needham, 1909 (Plecoptera: Peltoperlidae) from Guangxi of China, based on male, female, and larval stage. 258 records from (Tab. 8) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 79-547B, Mazagan Basin west of Morocco. 74 records from Revision of the Eurybrachidae XIV. The Australian genera Olonia Stål, 1862 and Stalobrachys gen. nov. (Hemiptera: Fulgoromorpha). 5 records from Revision of the Zethus luzonensis species-group (Hymenoptera: Vespidae: Eumeninae), with description of a new species. 6 records from Ontogeny as an important part of integrative taxonomy in tergipedid aeolidaceans (Gastropoda: Nudibranchia) with a description of a new genus and species from the Barents Sea. 11664 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 156 records from A taxonomic review of the genus Antepipona de Saussure, 1855 (Hymenoptera: Vespidae: Eumeninae) from India. 103 records from BIRDRACE federleser. 6937 records from Análisis de los efectos ecológicos del aprovechamiento forestal en el Corredor Biológico Mesoamericano: mamíferos, plantas y sus interacciones. 4 records from Taxonomy of Litoria graminea (Anura: Hylidae), with descriptions of two closely related new species. 310 records from The Fishery Grounds near Alexandria.VII.Decapoda.By Heinrich Balss.(1936).Notes and memoirs No. 15. 1 records from Dinoflagellate abundance of Hole 38-343. 1 records from Dolichocephala Macquart of Thailand (Diptera: Empididae: Clinocerinae). 526598 records from CAS Botany (BOT). 70 records from Plasm bearing foraminifera counts from M35/1_MSN1059. 2291 records from (Table 3) Distribution of benthic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 106 records from (Table 1) Abundance of live benthic foraminifera in surface sediments of the Arctic Ocean. 508 records from Barents Sea Zooplankton – March and May 1998 and July 1999. Zooplankton sampling on board the Norwegian R/V Jan Mayen, program ALV. 12 records from List of Lizard species recorded in Vava'u during BioRAP. 201 records from Range table from benthic foraminifers in ODP Hole 198-1207B. 9 records from Sarcodine counts and carbon biomass at station TT007_7-CTD76. 178 records from (Fig. 3) Relative abundance of Neogloboquadrina pachyderma (s) in sediment core MD99-2343. 1306 records from Relevé de collections de lépidoptères rhopalocères et de coléoptères saproxyliques.. 195 records from Catalogue of the herbarium specimens collected from Discovery Bay and Runaway Bay, Jamaica, West Indies, 1958-1999.. 5005 records from Planktic foraminifera abundance of Hole 15-147. 131 records from Range table from planktonic foraminifers in ODP Hole 175-1084A. 148 records from Mean density of total metazoan meiofauna and major taxa or groups in the top 10 cm of surface sediment on 25 different dates at DYFAMED station. 3 records from New species of Prolachesilla Mockford & Sullivan (Psocodea: ‘ Psocoptera’: Lachesillidae: Graphocaeciliini) from Bolivia and Mexico. 21319 records from Tartu University, palaeontology collections. 1 records from A new moss salamander, genus Nototriton (Caudata: Plethodontidae), from the Cordillera de Talamanca, in the Costa Rica-Panama border region. 3387 records from Données avifaune de Guadeloupe. 135 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 10 records from Range table from planktonic foraminifers in ODP Hole 172-1057A. 22433 records from UMNH Reptiles and Amphibians Collection (Arctos). 4 records from Gymnothorax pseudotile sp. nov. (Muraenidae: Muraeninae) from Bay of Bengal India. 491 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 2432 records from (Table T1) Calcareous nannofossil stratigraphy of ODP Hole 198-1207A. 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 100422 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 186 records from DBG Tissue and DNA Bank. 114 records from BIRDRACE Di-Bi-Di-Birder. 475 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 128 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Aves Nidos (MFA-ZV-Or-N). 5 records from A taxonomic revision of the genus Oxyopomyrmex André, 1881 (Hymenoptera: Formicidae). 229 records from (Table 2) Palynological group observed in ODP Site 170-1039 samples. 209 records from Database_Dragonflies_ Madagascar Biodiversity Center PBZT. 2975 records from HerbarioHerrerense. 133 records from Nematode abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 9 records from Dinoflagellate abundance of Hole 71-513A. 203 records from Microzooplankton abundance measured on water bottle samples at station PS58/048-3. 31917 records from Mollusca of Costa Rica (INBio). 207 records from Total foraminifera counts of multinet SO118_MSN1253. 2 records from Two new species of Prionomastix Mayr (Hymenoptera: Encyrtidae) with a key to Indian species. 2 records from Phylloicus mirabilis (Trichoptera: Calamoceratidae), a new species from Rio de Janeiro state, southeastern Brazil. 6288 records from Macroinvertebrate abundance data from the littoral zone of a number of large New Zealand lakes. 1278 records from Foraminifera abundance of Hole 45-396. 10 records from Ice Amphipods Canada Basin. 962 records from Distribución y algunos aspectos ecológicos de hongos hidnoides estipitados de México. 5355 records from (Figure 4) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-549A. 260 records from Miljodir_naturtypekartlegging_2017. 1 records from Revision of Thaumatocranaus Roewer, 1932, with description of two new species (Opiliones: Laniatores: Gonyleptoidea). 5 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR16. 20674 records from CPAP - Herbário CPAP. 576 records from (Table 6) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-683A, Part II. 34 records from Freshwater Gastropods of Taveuni. 11701 records from EAFM - Herbário do Instituto Federal de Educação, Ciência e Tecnologia do Amazonas. 106 records from Planktic foraminifera abundance of Hole 1-2. 1 records from The genus Neoheegeria with a new species from Iran exhibiting wing-dimorphism (Thysanoptera: Phlaeothripidae). 340 records from Harpactus Shuckard. 2497 records from Los crustáceos decápodos marinos: Actualización de la colección carcinológica de la Facultad de Ciencias Biológicas, UANL. 63 records from (Data S1) Palynology of ODP Site 119-739. 1005 records from (Table 1) Distribution of Pleistocene calcareous nannofossils in ODP Hole105-646A. 41 records from List of Snail species in Vava'u. 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 3 records from Microplankton counts and carbon biomass at station TT011_3-CTD33. 381 records from Estudio taxonómico de moluscos terrestres y dulceacuícolas de la región maya de México I. Reserva de la Biosfera Pantanos de Centla. 3050 records from Distribution of dead benthic foraminifera in surface sediments of the Norwegian Sea (Table 3). 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 324 records from Alterra (NL) - Microarthropods inventory in Heathland. 314 records from Peces laguna El Tinije. 9 records from A review of the spider genus Singaporemma (Araneae: Tetrablemmidae), with the description of a new species. 226 records from Total foraminifera counts of multinet M21/1_MSN610. 1178 records from Malawi-Noctuidae-Biodiversity. 1665 records from (Table 3C) Distribution of Mesozoic nannoliths at DSDP Hole 43-384. 3281 records from National Earthworm Recording Scheme Records (Great Britain). 17241 records from Données naturalistes de Julien BIRARD. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 4 records from Spiders of the São Paulo state islands, Brazil: redescription of Stenoterommata crassimana (Mello-Leitão, 1923) n. comb. (Araneae, Nemesiidae). 46 records from Revision of the subgenus Dicranomyia (Erostrata) Savchenko, 1976 (Diptera, Limoniidae) of Japan. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 250 records from Microplankton abundance in the euphotic zone of the Aegean and Levantine Seas in August-September 1989. 27 records from Données naturalistes de Jean-Michel SZCZYT. 80 records from (Table 2) Abundance and biomass of the main microplankton biota components in the Murmansk coastal pelagic zone in March 1998. 414 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE233. 2259 records from Invertebrate specimens in the Wakayama Prefectural Museum of Natural History, Japan.. 105 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Thiankoye) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1938 records from Vascular plant specimens of Shirakami Institute for Environmental Science, Hirosaki University. 268 records from Range table from planktonic foraminifers in ODP Hole 180-1109D. 1 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 914 records from Suivi des amphibiens dans les forêts de la CREA. 9449 records from Fern (Pteridophyta) specimens of Toyama Science Museum. 9 records from Calculated abundance and biomass of Ophiocten gracilis at different stations on Kolbeinsey Ridge. 153570 records from Merseyside BioBank (unverified). 11 records from Analyses of the recent components of sediment core PS1215-2. 669 records from Abundance of large foraminifera in cores from transect HYD-01C, IODP Expedition 325. 348 records from Données d'occurrences des spécimens des plantes menacées du Sénégal conservés à l'Herbier de l'IFAN.. 1110 records from HFSL-Fungos - Herbário Dr. Ary Tupinambá Penna Pinheiro - Fungos. 415 records from Araneae on grasslands 2008. 30 records from A new species and three newly recorded species of the dacnusine genus Dacnusa Haliday (Hymenoptera: Braconidae: Alysiinae) from China. 5920 records from Alterra (NL) - Microarthropods inventories by Henk Siepel on various locations. 13 records from Microzooplankton abundance and biomass at station NBP97-08-04-5. 4944 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 123 records from Total foraminifera counts of multinet M11/1_MSN517. 139 records from Inventario de Aves en la Finca la Reserva, Yopal, Casanare. 155 records from Total foraminifera counts of multinet M42/3_MSN1361. 424 records from Bird Collection of Yokosuka City Museum. 43388 records from Herpetology Collection - Royal Ontario Museum. 2 records from Three new species of tribe Odynerini (Hymenoptera, Vespidae, Eumeninae) from the Neotropical Region. 70281 records from Museu Paraense Emilio Goeldi - Hymenoptera Collection. 3 records from A new species of Theretra Hübner (Lepidoptera: Sphingidae) from the southern Western Ghats, India. 21 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 1 records from A revision of the Neotropical eumenine wasp genus Stenosigma Giordani Soika, 1978 (Hymenoptera, Vespidae). 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 187670 records from Florida Keys Reef Visual Census 2003. 378 records from Fels- und Weinbergsflächen in Hatzenport/Terrassenmosel. 14 records from New species of Endecous (Grylloidea, Phalangopsidae, Luzarinae) from the Iguaçu National Park (Brazil), including bioacoustics, cytogenetic and distribution data. 43424 records from Herbarium of Jyväskylä University Museum. 569 records from Planktic foraminifera abundance of Hole 94-606. 254 records from Grünes Germersheim. 26 records from Morphological convergences in Ameles Burmeister and Pseudoyersinia Kirby: Taxonomic implications of wing reduction and flight predisposition in some West-Mediterranean Amelini (Insecta: Mantodea). 4 records from The Afrotropical Miomantis caffra Saussure 1871 and M. paykullii Stal 1871: first records of alien mantid species in Portugal and Europe, with an updated checklist of Mantodea in Portugal (Insecta: Mantodea). 1342 records from (Table 2) Distribution of calcareous nannofossils in the Paleocene of ODP Hole 113-689B. 1632 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 7 records from Distribution of planktic foraminifera of sediment core GIK23342-6 at stadium 5.5. 50 records from Antarctic Starfish (Echinodermata: asteroidea) from the ANDEEP3 expedition. 94 records from Nationalpark Jasmund. 221 records from (Table 1) Distribution of ice-rafted fossils in ODP Hole 104-642B. 2382 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del piedemonte de Arauca, municipio de Tame. 1483 records from Données d'occurrence du dispositif Megascope - Observatoire PELAGIS UMS 3462. 1 records from Review of the Maluku Islands species of the lanternfly genus Birdantis Stål, 1863, with a new species and identification key (Hemiptera: Fulgoromorpha: Fulgoridae). 3 records from Genera of Mythicomyiidae (Insecta, Diptera) new to the fauna of Morocco, with descriptions of new species. 2024 records from Tejidos de insectos recolectados en trampas Malaise en los departamentos de Santander, Antioquia y Vichada - Proyecto Colombia Bio. 104 records from Kamptozoa collection of National Museum of Nature and Science. 1668 records from MCNH Museum of Cultural and Natural History Fish Collection. 182 records from Biodiversity and notes on carabid beetles from Angola with description of new taxa (Coleoptera: Carabidae). 249 records from Schule Sulzbach (Oberegg). 1934 records from Planktic foraminifera abundance of Hole 72-518. 3153 records from Gunma Museum of Natural History, Molluscan Specimen. 80 records from BIRDRACE Falkenberger Fluppis. 226 records from Tejidos colectados en la ventana Beltrán, corregimiento Paquiló, Municipio de Beltrán, Cundinamarca. 14 records from Analyses of the recent components of sediment core PS1220-3. 662 records from Snipe survey of key sites in Britain in 2006. 41 records from Revision of the Madagascan endemic Homollea (Rubiaceae - Pavetteae), with description of two new species. 27 records from Meiobenthos abundance in the bottom sediments of the Bosporus area. 2 records from Two new genera of predatory katydids (Orthoptera: Tettigoniidae: Meconematinae) from the Amazon rainforest. 2 records from A new cave-dwelling species of the genus Mesoiulus Berlese, 1886 (Diplopoda, Julida, Julidae) from Turkey. 4 records from Ansienulina, a new genus of jumping spiders from tropical Africa (Araneae: Salticidae: Thiratoscirtinae). 9996 records from (Appendix B1) Relative abundances of middle Eocene-late Oligocene calcareous nannofossils in ODP Hole 120-748B. 16 records from Im und um das Schulhaus. 204 records from Données naturalistes d'Arzhvaël JEUSSET. 14370 records from CSIRO, South East Fishery Habitat Ecosystem Study, Southeast Australia, 1993-1997. 20 records from Nannofossil abundance of Hole 2-9. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 298 records from Measurements of elephant tusk trophies taken in Botswana 2012. 137 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 31 records from Content of coarse fraction and G. menardii in sediment corev V25-63. 60 records from A revision of the genus Pochytoides Berland & Millot, 1941 (Araneae: Salticidae), with descriptions of six new species. 4625 records from Range table from planktonic foraminifers in ODP Hole 152-918A. 830 records from High occurrence of jellyfish predation by black-browed and Campbell albatross identified by DNA metabarcoding 2017. 772 records from Freshwater Lamprey Survey Data. 3427 records from Occurrence of 13 crabeater seals (Lobodon carcinophaga) from ARGOS satellite track observations during campaign DRE1998. 1083 records from Diversidad de Mariposas en la Reserva Natural El Romeral. 6351 records from Gwaii Haanas Marine Plants (OBIS Canada). 189 records from (Appendix E) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 161-976C. 20430 records from Distribution de quelques espèces de plantes agroforestières et médicinales au Bénin. 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 11 records from First Canadian record of the water mite Thermacarus nevadensis Marshall, 1928 (Arachnida: Acariformes: Hydrachnidiae: Thermacaridae) from hot springs in British Columbia. 1216 records from "Répertoire des Forêts sacrées dans les Départements de l’Ouémé et du Plateau. Data mobilized in the framework of JRS Biodiversity Foundation project. 23 records from Páramo de Belmira as an important centre of endemism in the northern Colombian Andes: new evidence from Pronophilina butterflies (Lepidoptera: Nymphalidae, Satyrinae, Satyrini). 826 records from DASSH Data Archive Centre expert sightings records. 46 records from Review of fungus-feeding urothripine species from China, with descriptions of two new species (Thysanoptera: Phlaeothripidae). 38364 records from Plants of Ghana. 15964 records from RNF - Association Loiret Nature Environnement. 1578 records from Benthic foraminiferal assemblages across the Cretaceous Paleogene boundray of ODP Site 208-1262 on Walvis Ridge, eastern South Atlantic. 64143 records from Michigan State University Herbarium Vascular Plants. 25 records from A new species of the genus Anthaxia (Anthaxia) (Coleoptera: Buprestidae) from The Islamic Republic of Iran. 1936 records from Reports of New Zealand Flatworms in Scotland, 1989 - 2005. 61 records from Total foraminifera counts of multinet M21/4_MSN698. 19 records from Review of the Asian species of the subgenus Neocheilosia Barkalov (Diptera, Syrphidae), with description of new species. 31 records from Fragment size of individual Fagus sylvatica trees based on microsatellite markers. 554 records from Prélèvements Cerf de Java en Nouvelle-Calédonie. CEN_Nouvelle-Calédonie. 2 records from A review of the genus Saccharicoccus Ferris, 1950 (Hemiptera: Coccomorpha: Pseudococcidae) in China, with description of a new species. 51 records from PNG Invasive Species. 287 records from (Table 3) Numerical abundances of nannofossil taxa in ODP Hole 126-791A. 4 records from Austrosciara Schmitz & Mjöberg, 1924, a senior synonym of Ctenosciara Tuomikoski, 1960 (Diptera: Sciaridae) and the description of a new brachypterous species in the genus. 61835 records from Données d'occurrence Espèces issues de la base Natura 2000 : espèces d'intérêt communautaire et autres espèces remarquables renseignées dans les FSD. 13 records from Review of Australian genera Tessaromma Newman and Phlyctaenodes Newman with description of a new genus and species (Coleoptera: Cerambycidae: Cerambycinae: Phlyctaenodini). 2340 records from (Table 2) Distribution of microfossils in the Barrow Group of ODP Site 122-763. 309 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE218. 102 records from Microzooplankton abundance measured on water bottle samples at station PS65/587-1. 278 records from Código de barras genético de cinco grupos críticos de la flora de México. 4808 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 54 records from VESS Vanuatu seagrass specimens. 4312 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 103 records from Total foraminifera counts from M35/1_MSN1044. 30 records from Smear slide analysis on sediment core GeoB4206-1. 284 records from Revision of the genus Draconarius Ovtchinnikov 1999 (Agelenidae: Coelotinae) in Yunnan, China, with an analysis of the Coelotinae diversity in the Gaoligongshan Mountains. 4 records from Abundance of microplankton from bottle APRIL-2000-K5. 49022 records from Dreal Corse - Base Ogreva. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 37 records from Distribution of meiobenthos in surface sediments of the northeastern Atlantic (Table 1). 61 records from A conspectus of the silver-flies (Diptera: Chamaemyiidae) of the Middle East with descriptions of new species of Chamaemyia Meigen and Melanochthiphila Frey, from the Arabian Peninsula. 25 records from Catochini, Strobliellini and Acoenoniini revisited: a taxonomic review of the small tribes of the Micromyinae (Diptera: Cecidomyiidae). 5048 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 6 records from Sarcodine counts and carbon biomass at station TT011_10-CTD123. 8231 records from Estatus de conservación y riesgo sanitario de las poblaciones nativas de abejorros del género Bombus en México 1a etapa. 27291 records from Amphibian Specimens. 66 records from Rhopalocera of Martinique. 65 records from The genus Clubiona Latreille, 1904 (Araneae: Clubionidae) in the Maghreb, with notes on the genevensis group and new records from the Mediterranean Region. 84 records from BIRDRACE Bielefinken. 6 records from On European Spiders Of The Nominal Families Liocranidae, Miturgidae And Zoridae (Araneae), With Descriptions Of New Taxa. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1985 (réseau Ongulés sauvages ONCFS-FNC-FDC). 44 records from Phytoplankton abundance in surface water in 1997, Ancon, Peru. 89918 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 18 records from Microzooplankton abundance and biomass at station TT043_7-20. 2477 records from Distribution of benthic foraminifera of sediment core PS1388-3. 112 records from Caracterización de Flora de la Reserva Forestal Protectora Regional Brisas del Rincón. 324 records from Phytoplankton abundance measured on water bottle samples at station PS65/470-1. 966 records from (Table 2) Distribution of nannofossils in DSDP Hole 87-583. 4 records from Distribution of meiobenthos in sediment core M23_149 of the northeastern Atlantic (Table 1). 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 455 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 11438 records from Données naturalistes de Jérôme BARBUT. 138 records from (Figure 1) Stratigraphic distribution of taxa at DSDP Hole 79-547B. 8 records from The freshwater snake eel genus Lamnostoma (Anguilliformes: Ophichthidae) in Taiwan, with description of a new species. 329 records from Bird Collection of Otto Hedin. 1029 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 13 records from Distribution of meiobenthos in sediment core M23_203 of the northeastern Atlantic (Table 1). 3 records from Two new South American species of Monomorium Mayr with taxonomic notes on the genus.. 1 records from Microplankton counts and carbon biomass at station TT011_12-CTD150. 1974 records from PINK - Amphibia monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 315 records from Liberia Forest Elephant National Action Plan Data. 9 records from Distribution of meiobenthos in sediment core M19_197-2 of the northeastern Atlantic (Table 1). 108 records from Artsrike vegkanter i Haugesund. 42 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 9391 records from Levantamento de Mamíferos do Parque Nacional da Quiçama - INBAC/RWCP - 2017. 2 records from URBALP_2017_12_18. 322 records from Pollen profile from sediment core AV14_K2-4. 210 records from Range table from planktonic foraminifers in ODP Hole 159-961A. 66607 records from AUM Fish Collection. 10 records from A new species of Protaetia Burmeister, 1842 from Armenia with taxonomic notes on Cetonia floricola fausti Kraatz, 1891 (Coleoptera: Scarabaeidae: Cetoniinae). 2878 records from Banco de Vida/ CJ Amphibian Museum collection. 21 records from Antarctic and sub-Antarctic Lophogastrida occurrences. 53 records from Plasm bearing foraminifera counts of multinet M21/5_MSN740. 27 records from A Revision of the Genus Synagelides Strand, 1906 (Araneae, Salticidae) in Korea. 1527 records from Ghent University - Zoology Museum - Vertebrate collection. 20818 records from ARKO kulturmarkseng. 461 records from Arthropod specimens of Natural History Museum, Kishiwada City. 4 records from A new species of Brachylepis Kolbe, 1894 from Tanzania (Scarabaeidae: Melolonthinae: Leucopholini). 1288 records from DREAL_PACA_-_N2000_-_Conseil_Général_83_2017_12_18. 11 records from Cryptic diversity of the rocky crab genus Glebocarcinus Nations, 1975 (Crustacea: Decapoda: Cancridae): description of a new species from Russian coastal waters of the Sea of Japan based on morphology, DNA and distribution. 201 records from Total foraminifera counts of multinet M21/3_MSN663. 32 records from And then there were six: a revision of the genus Phanolinopsis Scheerpeltz (Coleoptera: Staphylinidae: Staphylininae). 3 records from Notomicrus petrareptans sp. n., a new seep-dwelling species of Noteridae from Suriname (Coleoptera: Adephaga). 11475875 records from Finnish Bird Ringing and Recovery Database. 2 records from Apectodinium spp. and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 182-1128D. 66 records from Winter Foraging Locations Of Southern Ocean Predators - sub-Antarctic islands 2008/09. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 2 records from A new species of Cyrtodactylus (Squamata: Gekkonidae) from Ninh Binh Province, Vietnam. 82128 records from New Zealand Fungal and Plant Disease Collection (PDD). 5226 records from Mamíferos de Nuevo León: distribución y taxonomía. 5 records from A new species of Miroculis Edmunds, 1963 (Ephemeroptera: Leptophlebiidae) from Cerrado-Amazonian forest transition zone, Brazil. 546 records from Ecosystem biomonitoring with eDNA: metabarcoding across the tree of life in a tropical marine environment. 219 records from Umgebung der Grundschule Oderberg. 935 records from Planktic foraminifera abundance of Hole 26-251A. 3 records from The family Hyalidae (Crustacea: Amphipoda: Talitroidea) from Korean waters. 2. Genus Protohyale Bousfield & Hendrycks, 2002. 606 records from Patrones de diversidad florística y faunística del área focal Ixcan, selva Lacandona, Chiapas. 1618 records from Ganadería Colombiana Sostenible (escarabajos coprófagos 2017). 4195 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 17 records from New species of Lachesilla (Psocodea: Psocomorpha: Lachesillidae), in species group corona, from southern Mexico and Central America. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 737 records from Phytoplankton abundance in surface water in February 1998, Pisco, Peru. 3 records from New Antarctic stenothoids sensu lato (Amphipoda, Crustacea). 4229 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 1567 records from Museu Paraense Emílio Goeldi - Mollusca Collection. 582 records from Distribution of planktic foraminifera (200-630 µm) of sediment core M8_057-2 (Table 4). 2 records from First record of the tropical genus Rambutanura (Collembola: Neanuridae: Neanurinae) in Palearctic, with description of a new species from China. 268 records from Total foraminifera counts of multinet M6/7_MSN125. 827 records from Mirmecofauna de la reserva ecológica de San Felipe Bacalar. 86 records from Oiseaux(Faune des mangroves et des zones humides du sud Togo). 216 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V27-20. 7141 records from flower visitor interactions 2008. 1519 records from Nannofossil abundance of Hole 40-362. 2813 records from Amphibiens et Reptiles de Martinique (données Michel Breuil). 693 records from (Appendix A1) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1209B in the central Pacific. 312 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1992. 73 records from VFD-HH/SH: Pferdweide Lammert. 147 records from Total foraminifera counts of multinet M21/3_MSN674. 288 records from Conocimiento de la diversidad y distribución actual del maíz nativo y Tripsacum en el estado de Tamaulipas. 3 records from New species and records of ptyctimous mites (Acari, Oribatida) from the Philippines. 74192 records from Data-set of Moth Specimen from TESRI. 91 records from BIRDRACE NABU LV Hessen. 860 records from Phytoplankton measured on water bottle samples during THALASSA cruise PROSOPE. 1 records from Description of two new Capnia species (Plecoptera: Capniidae) from the Hengduan Mountains of southwestern China. 8 records from Dendrogramma, New Genus, with Two New Non- Bilaterian Species from the Marine Bathyal of Southeastern Australia (Animalia, Metazoa incertae sedis) – with Similarities to Some Medusoids from the. 7044 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 1133 records from Wood-inhabiting corticioid basidiomycetes in Norway. 128 records from Ostracod abundance in sediment core Lz1120. 92 records from Planktic foraminifera assemblage in sediment core GIK23071-2. 1122 records from Collection plants of Sochi park "Dendrarium". 11 records from BenthosBarentsSeaPolarstern1991. 1091 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 10610 records from CSIRO, fish surveys by the Courageous, 1978-1979. 8 records from A study of the genus Agrilaxia Kerremans, 1903 from French Guiana (Coleoptera: Buprestidae: Anthaxiini). 113 records from Liether Kalkgrube. 4 records from Four new species of the spider genus Leclercera Deeleman-Reinhold (Araneae, Ochyroceratidae) from Nepal. 3 records from Two new species of Protonemura (Plecoptera: Nemouridae) from China, with biogeographical notes on the genus. 1828 records from Collection Foraminifera SMF. 10581874 records from OEH Atlas of NSW Wildlife. 37136 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 12 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC3. 185 records from (Table 8) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-217. 942 records from (Table 3) Distribution of benthic foraminifers in the > 63 µm fraction in surface sediments from the central Arctic Ocean. 4 records from Sycidiphaga, a new genus of Sycophaginae Walker, 1975 (Hymenoptera, Chalcidoidea, Agaonidae) associated with Ficus subgenus Sycidium in southern China. 358 records from Caracterización de fauna para el establecimiento de nuevas Reservas Naturales de la Sociedad Civil en Arauca. 10 records from Analyses of the recent components of sediment core PS1014-1. 3 records from Diagnosis of Calagasma Bergroth and Epipedus Spinola with description of Calagasma eclipsa sp. nov. and Epipedus rolstoni sp. nov. (Hemiptera: Heteroptera: Pentatomidae: Pentatominae: Carpocorini). 204 records from HeathNet data. 17592 records from Inventaire permanent des invertébrés de Haute-Normandie. 101 records from Steinbruch Kronungen. 2 records from Description and phylogenetic position of a new species of Nematanthus (Gesneriaceae) from Bahia, Brazil. 14775 records from DREAL_PACA_-_N2000_-_Commune_de_Névache_2017_12_18. 22 records from Reappraisal of Synagrops Günther, 1887 with rehabilitation and revision of Parascombrops Alcock, 1889 including description of seven new species and two new genera (Perciformes: Acropomatidae). 7 records from Synonymy of some Cicadellidae (Hemiptera: Auchenorrhyncha) known from Tuva Republic of Russia. 2 records from On Sphallambyx mexicanum and key to species of Sphallambyx (Coleoptera, Cerambycidae, Cerambycinae). 80 records from Lahnufer in Villmar. 1970 records from peqrb_c_populationandcommunitydynamics_2001-2011. 82 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB01 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 113 records from Abundance of calcareous dinoflagellates of sediment core GeoB1117-2. 484 records from National Taiwan Ocean University. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 571 records from Pollen profile from Arrington Marsh. 520 records from SNH Invertebrate Site Condition Monitoring 2015-16: Rum SSSI. 10202 records from Coleoptera specimen database of Osaka Museum of Natural History. 5638976 records from UK Butterfly Monitoring Scheme (UKBMS). 844 records from Données sur les Poissons de Mayotte (passe en S et passe de Bandrélé). 103 records from Range table from planktonic foraminifers in ODP Hole 171-1050A. 3659 records from Herpetology Collection NRM. 69 records from Planktic foraminifera abundance of Hole 18-182. 6 records from Content of coarse fraction and G. menardii in sediment corev V25-48. 1 records from A new species of Limnephilidae (Insecta: Trichoptera) from the Western Alps (Insecta: Trichoptera). 3320 records from (Figure 4) Distribution and relative abundances of the benthic foraminifers recovered from the Jurassic section of DSDP Hole 79-547B. 817 records from Planktic foraminifera abundance of Hole 94-607. 27 records from Angelberger Forst - Klassen 3 a und 3 b. 2987 records from Pteridophyta specimens of Iwate Prefectural Museum. 5465 records from (Table 1) Distribution of benthic foraminifera on sediment core PS2837. 2392 records from (Appendix B) Foraminifera and stable carbon and oxygen isotope record of ODP Hole 105-647B. 187 records from Diversity of total live benthic foraminiferal assemblages in South Atlantic surface sediments. 1 records from A new species of Crinibracon Quicke (Hymenoptera: Braconidae) parasitic on pupae of Hasora chromus (Cramer) (Lepidoptera: Hesperiidae) from India. 17 records from Meiofauna abundance in sediment core 13200-024. 60 records from Total foraminifera counts of multinet FCA97C_MSN1344. 93 records from Anfibios de un sector del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO- 2017. 3 records from A new species of Campylothorax Schött, 1893 (Collembola, Paronellidae) from Brazilian Amazon, with an identification key to the genus. 1871 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 4251 records from Atlas de la flore de Lorraine. 2081 records from Collection Polychaeta - ZIM Hamburg. 369 records from Diatom abundance measured on water bottle samples at station PS58/038-3. 882 records from (Table 4) Distribution of middle Eocene calcareous nannofossils in ODP Hole 149-897D. 6 records from A New Bent-toed Gecko (Cyrtodactylus: Squamata: Gekkonidae) from the Island of Tanahjampea, South Sulawesi, Indonesia. 635 records from Nereididae (Annelida: Polychaeta) de México. 24 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 3805 records from Lichen specimens of National Museum of Nature and Science (TNS). 1163 records from Detección de reclutas de la dorada Sparus aurata como medida del nivel de establecimiento en la Bahía de La Paz, BCS. 124 records from (Table S1) Distribution of Florisphaera profunda in surface sediment samples. 91 records from EDP Foz Tua: Terrestrial Vertebrates Baseline_studies (EIA) [2006]. 121 records from Table II: Birds observed at the Weddell Sea during the period: 22 December 1959 to 14 January 1960. 1 records from Dexoris ruzzieri sp. nov. (Coleoptera: Lycidae), a new net-winged beetle from Ivory Coast. 307 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 15124 records from Données naturalistes de Philippe KEITH. 243 records from Anfibios y reptiles del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 152 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 267 records from Range table from benthic foraminifers in ODP Hole 141-861D. 31 records from Regenwasserabfangbecken. 162 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 17 records from Collection Bryozoa - ZIM Hamburg. 61 records from Foraminifera species abundances from tow TT007_5-MOC9. 99 records from Naturalis Biodiversity Center (NL) - Museum collection digitized at storage unit level. 756 records from Especies de Anopheles en el sur de México y su distribución geográfica actual con enfoque en taxonomía clásica y molecular. 1 records from The rare deep-living hyperiid amphipod Megalanceoloides remipes (Barnard, 1932): complementary description and symbiosis. 1037 records from Distribution of planktic foraminifers of core V19-29. 208485 records from Mayfly (Ephemeroptera) Data for Great Britain for 1906-2017. 168 records from STAMP seabird egg collection. 18 records from A cybercatalogue of American sand fly types (Diptera, Psychodidae, Phlebotominae) deposited at the Natural History Museum, London. 7399 records from Marine invertabrate(ARTHROPODA) specimen database of Osaka Museum of Natural History. 62428 records from Microlepidoptera of Glamorgan. 80 records from Planktic foraminifera abundance of Hole 49-411A. 184 records from Nannofossil abundance of Hole 14-139. 202 records from BTCV wildlife counts recording workshops. 2 records from Description of lithologic section units of IODP Hole 325-M0049A. 3 records from Two new species of Brasineura Silva-Neto & García Aldrete (Psocodea, ‘ Psocoptera’, Ptiloneuridae), from Brazil. 2808 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 182 records from Taxonomía e inventario de cianofitas del orden chroococcales (Cyanophyceae). 2 records from A new species and a new record of Pelthydrus Orchymont, 1919 from Yunnan, China (Coleoptera: Hydrophilidae: Hydrophilinae). 391 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 1590 records from Survey of distribution of beavers in Tayside in 2012. 1 records from A new species of the genus Tetratoma Fabricius (Coleoptera, Tetratomidae) from China. 7 records from Nannofossil abundance of Hole 29-278A. 1222 records from Scientific Results of the New Zealand Government Trawling Expedition, 1907. 283 records from Données naturalistes de Pierre NOEL (M2MNHN2010). 128 records from (Figure 3) Foraminiferal assemblages recovered from DSDP Hole 79-547B. 184 records from Monitoreo biológico en la cuenca RUT, campaña ARA - RARE - CVC – Asociación Calidris. 4 records from Two new species of Clubiona Latreille (Araneae: Clubionidae) from China. 16518 records from RNF - Données du CEN Limousin. 52 records from Nannofossil abundance of Hole 27-259. 53 records from SNH Invertebrate Site Condition Monitoring 2015: Maidens to Doonfoot SSSI. 9 records from Five new species of the leafhopper genus Thagria Melichar (Hemiptera: Cicadellidae: Coelidiinae) from China. 56 records from Kindervilla Aussengelände/ Hiltroper Park. 5948 records from (Appendix 1) Census data of planktic foraminiferal faunas together with estimates of mean annual SST for ODP Site 181-1123. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 1852 records from Inventario de los crustáceos decápodos asociados al ecosistema coralino de Pocillopora en el Pacífico tropical mexicano. 2958 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México. 530 records from (Appendix B3) Calcareous nannofossils of ODP Site 208-1263. 193 records from Herbario IES San Isidoro de Sevilla. 989 records from Range table from benthic foraminifers in ODP Hole 189-1170A. 913 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 14 records from A new genus and species of cardinalfish (Percomorpha, Apogonidae, Sphaeramiini) from the coastal waters of Vietnam: luminescent or not?. 172 records from (Table 4) Numerical abundances of nannofossil taxa in ODP Hole 126-792A. 27 records from New species of Brachiacantha Dejean, 1837 (Coleoptera: Coccinellidae) from Mexico and Central America. 1672 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 159 records from Australian Platypus Conservancy. 22 records from Planktic foraminifera abundance of Hole 29-284A. 5356 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 1716 records from Elaboración del banco de datos de las colecciones del Museo de Zoología-CIQRO. 17 records from Descriptions of larvae of three species of Hydropsyche (Trichoptera, Hydropsychidae) from China. 504 records from (Figure 10) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-537. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 275 records from Phytoplankton abundance at several stations in January 2005, Chipana, Chile. 147 records from NABU-Auerochsenweide. 17 records from Benthic foraminifera abundance of Hole 11-108. 141 records from Assemblage of living benthic foraminifera in sediment core GeoB3715-1. 505 records from Range table from planktonic foraminifers in ODP Hole 155-942A. 6609 records from Echinoids_occurrences_Southern_Ocean. 1102 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832A. 73369 records from University of British Columbia Herbarium (UBC) - Algae Collection. 473 records from Range table from planktonic foraminifers in ODP Hole 182-1131A. 6 records from Analyses of the recent components of sediment core PS1279-1. 457 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE278. 274 records from Fremmede arter - Planteimport, Engebråten Planteskole. 16 records from Palau Invasives. 195 records from Phytoplankton samples - 2001/02 V7 LOSS. 2094 records from (Table 16) Calcareous nannofossil occurrences in ODP Hole 130-805B. 36632 records from imr_mareano_grab. 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 34 records from A new Peruvian species and new records of the genus Piestus Gravenhorst (Coleoptera: Staphylinidae). 10 records from Revision of the Neotropical moth genus Ptychotrichos Schaus (Lepidoptera, Erebidae, Arctiinae, Arctiini, Ctenuchina). 10465 records from Stoneflies (Plecoptera) of Ireland. 3606 records from Temporal evolution of zooplankton, surface observations, in the Northwestern Mediterranean Sea, Villefranche-sur-mer 1898-1917. 7 records from Données naturalistes de Nicolas LEGRAND. 14549 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 2 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 82 records from Range table from planktonic foraminifers in ODP Hole 151-913A. 24 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2003. 4 records from Microzooplankton abundance and biomass at station TT050_19-3. 451581 records from Florida Keys Reef Visual Census 2009. 3370 records from Biodiversity assessment in the Yangambi Biosphere Reserve. 8347 records from RNF - Données de l'association de la RN du lac de Remoray. 62 records from Phytoplankton abundance at station Casma_2003-03-13_1, Casma, Peru. 107 records from Revision of the genus Callipia Guenée, 1858 (Lepidoptera, Geometridae), with the description of 15 new taxa. 2627 records from Data on medicinal plants of Benin. 10 records from Données naturalistes d'Emmanuel LESUISSE. 84 records from (Table 4) Meiofauna abundance in surface sediments of Cape Fear. 2163 records from PAMP-tracheo: Vascular plants in Pamplona and surroundings (Navarra, Spain). Undergraduate thesis, R. Mayo. 21 records from Planktic foraminifera abundance of Hole 16-161A. 9450 records from Arctic Species Trend Index (ASTI) : Freshwater. 235250 records from ABV - Common breeding birds in Flanders, Belgium. 34 records from Total foraminifera counts of multinet M21/4_MSN715. 1006 records from BioGIS - Fish - HUJ collections. 3 records from A new genus and species of praying mantis (Insecta, Mantodea, Mantidae) from Indochina, with a key to Mantidae of South-East Asia. 2 records from Revised checklist of the butterflies of Serbia (Lepidoptera: Papilionoidea). 168 records from Coleção de Platyhelminthes do Museu Nacional - UFRJ. 1096 records from Absolute abundance of particles and planktic foraminifera in sediment core GIK12310-4, Cape Barbas, North-West Africa (Appendix Tab. 2c). 143 records from Variabilidad genética en las poblaciones naturales de la almeja catarina Argopecten ventricosus-circularis (Sowerby II, 1842). 1 records from Leaf insects from Luzon, Philippines, with descriptions of four new species, the new genus Pseudomicrophyllium, and redescription of Phyllium (Phyllium) geryon Gray, 1843, (Phasmida: Phylliidae). 334 records from Listado florístico y etnobotánico de las plantas medicinales de los huicholes del río Chapalagana, Jalisco y del Nayar, Nayarit. 360 records from Bee species data, InsectScale 2008. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-14, >125 µm fraction. 51074 records from Karplanter i vernet barskog og edelløvskog. 16341 records from Marine Species Records from Skomer Marine Conservation Zone (MCZ) Marine Monitoring Programme. 3818 records from Inventarios de fauna y flora en los DRMIs Embalse Peñol - Guatapé y Cuenca Alta del Río Guatapé, Las Camelias y el área a declarar Cuenca de San Pedro. 419 records from Planktic foraminifera abundance of Hole 94-609B. 13 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2163-1. 1560 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 130-807C. 484 records from Données naturalistes de Martin HILAIRE. 882 records from (Appendix A4) Relative abundances of planktonic foraminifera of sediment core GeoB1706-2. 110 records from New distributional data on aquatic and semiaquatic bugs (Hemiptera: Heteroptera: Gerromorpha & Nepomorpha) from South America. 320 records from Measurements of elephant tusk trophies taken in Botswana 2013. 21 records from Description of lithologic section units of IODP Hole 325-M0053A. 537 records from Planktic foraminifera abundance of Hole 84-570. 56 records from Lebensraum Walram. 3 records from Argia angelae (Odonata: Zygoptera: Coenagrionidae) sp. nov. from Chapada dos Guimarães, Mato Grosso, Brazil. 87 records from Additional list of gregarous Benin valuable species. 9882 records from Insect specimens of Hokkaido University. 552 records from Occurence of microfossils in Early Cretaceous sediments of DSDP Hole 25-249 (Tab. 1). 88 records from Inventario nacional de especies vegetales y animales de uso artesanal. 17654 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 2 records from Description of a new species of Cytaea Keyserling 1882 from Fiji (Araneae: Salticidae). 10336 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Macros. 92 records from Noble Chafer: Pre-BAP records prior to 1998. 4 records from Taxonomic revision of the New World genus Ariopsis Gill (Siluriformes: Ariidae), with description of two new species. 79 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1375. 32 records from Study on Tychini of Balkan Peninsula (Coleoptera, Staphylinidae, Pselaphinae). 318 records from ABC_Useful Plants Of Malawi; Species targated for charcoal and firewood. 15 records from Abundance of benthos infauna at station GIK23060-1. 345 records from (Table 1) Dinoflagellate cysts and acritarchs in upper Pliocene and Pleistocene sediments from ODP Hole 151-911A. 201 records from Total foraminifera counts from multinet M31/3_MSN907. 14352 records from NE Dung Beetle Project. 2 records from Taxonomy and distribution of the genus Trichomyrmex Mayr, 1865 (Hymenoptera: Formicidae) in the Arabian Peninsula, with the description of two new species. 1982 records from Cnidaria specimens of Ryukyu University Museum (Fujukan). 5 records from Phthiria vaganoides sp. nov. (Bombyliidae, Phthiriinae, Phthiriini) from Northern Iran with the first record of Phthiria fulva Meigen, 1804 reared from a lepidopteran and description of the pupa. 146 records from NERP Marine Biodiversity Hub, Theme 1 - Tasman Fracture Commonwealth Marine Reserve Pilot Study - Lobster Potting Component. 2311 records from Freshwater Pest Plants Observations. 2626 records from Données du Réseau d'observateurs des mammifères marins en mer de la Manche. 1551 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688E, Part II. 1513 records from Coleoptera of Kozienice Forest. 188 records from Foraminifera abundance of Hole 58-442A. 2333 records from Palynological estimation of ODP Hole 189-1172A. 1026 records from Distribution of major planktic foraminifer at Site 177-1088. 106 records from Phytoplankton abundance at station Rigel_2_2005-05 in May 2005, Chipana, Chile. 52417 records from Vascular plant specimens of Akita Prefectural Museum. 5 records from Balanophora coralliformis (Balanophoraceae), a new species from Mt. Mingan, Luzon, Philippines. 3818 records from (Table 2) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-652A. 5126 records from Planktic foraminifera counts (census) of sediment core MD96-2084. 177 records from Revision of the Anotylus sculpturatus group (Coleoptera: Staphylinidae: Oxytelinae) with descriptions of seven new species from China. 54 records from Range table from benthic foraminifers in ODP Hole 159-961A. 5583 records from All observations extracted from the Flora of Northumberland and Durham 1831. 3 records from Dinoflagellate abundance of Hole 38-339. 80 records from Planktic foraminifera abundance of Hole 22-213. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 73 records from Colección de Referencia de Poliquetos del Museo de Ciencias de la Universidad El Bosque. 14 records from Ektomycorrhiza species in a soil exchange experiment. 3013 records from Coleção de Polychaeta do Museu Nacional. 204 records from DREAL_PACA_-_N2000_-_Métropole_Nice_Côte_d'Azur_2017_12_18. 111 records from EPAMA "Vallée de la Meuse"/2006 (Etude ESOPE). 5704 records from Molluscs of the Gothenburg Natural History Museum (GNM). 232 records from Phytoplankton abundance at station CD47_3105C#4. 151 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/088-7. 27 records from Contribution to the cockroach genus Ctenoneura Hanitsch, 1925 (Blattodea: Corydioidea: Corydiidae) with descriptions of seven new species from China. 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 1 records from Marine Invertebrata specimens deposited in the Fukui City Museum of Natural History, Japan. 203 records from (Table 1) Numerical abundance counts of planktonic foraminifers and other biogenic constituents for ODP Hole 114-698A. 82 records from Various insect orders, NEF. 86 records from Distribution of the sand-ascidian Seriocarpa rhizoides in surface sediments of Josephine-Bank, North Atlantic (Table 4). 1215 records from Barcant Butterfly Collection - Riodinidae. 135656 records from Bird Conservation Targeting Project (BCTP) in the UK, 2006-2011. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 174 records from Abundance of planktic foraminifera at CTD station PS55/081-1. 9 records from First record of the monotypic genus Acanopsilus Kieffer, 1908 (Hymenoptera: Diaprioidea: Diapriidae) from the Eastern Palaearctic region. 16 records from Inventarios de Aves de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 6844 records from NATURALIA_2017_12_18. 148 records from Bayerische Donau - Neu Ulm. 1597 records from Inventaires PnrL "Etangs". 6132 records from R-Tipos - Herbário do Museu Nacional - Tipos. 585 records from Données naturalistes de Dominique GALLAIS. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 866 records from Range table from planktonic foraminifers in ODP Hole 138-847B. 996 records from Colección Limnológica del Chocó. 642 records from Estudio sistemático y ecológico del género Tigridia (Iridaceae). 2268 records from WA. 3313 records from Fungi Collection in BCRC. 5 records from Xanthichthys greenei , a new species of triggerfish ( Balistidae ) from the Line Islands. 184 records from A synopsis of the Euphaeidae (Odonata: Zygoptera) of Vietnam, with descriptions of two new species of Euphaea. 108 records from Microzooplankton abundance measured on water bottle samples at station PS65/522-1. 813 records from Mastofauna de la vertiente occidental (oeste) del Parque Nacional Pico de Orizaba, Puebla (Fase 1). 296 records from (Table 4) Relative abundance of benthic foraminifera in ODP Hole 112-684A. 210 records from Black grouse lek surveys in the Scottish Borders, 2010-2011. 852 records from La Colección de Poliquetos (Annelida: Polychaeta) de la Facultad de Ciencias Biológicas, Universidad Autónoma de Nuevo León. 3904 records from UCT: South Africa Seaweeds(1905-2008). 58 records from Phytoplankton abundance at station Sechin_2003-08-06_2, Casma, Peru. 223 records from Observation Cétacés GDEGem. 59 records from Nannofossil abundance of Hole 26-255. 19 records from (Table 1) Rodent (lemming and vole) densities in 5 study areas in the Canadian Arctic. 9 records from The Cephenniini of China. VIII. New species and new records of Cephennodes Reitter of Hunan, Jiangxi, Zhejian and Fujian (Coleoptera: Staphylinidae: Scydmaeninae). 156 records from PnrL "Chantiers Natures". 4350 records from Departamento de Biolog. Veg. II, Facultad de Farmacia, Universidad Complutense, Madrid: MAF. 2 records from Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 9689 records from PlantBank Records. 1924 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 26 records from A taxonomic revision of Chinese Cleopomiarus Pierce (Coleoptera: Curculionidae) with description of two new species. 131 records from Abundance of planktic foraminifera at CTD station PS55/083-1. 874 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea, in 2009. 126 records from Planktic foraminifera assemblage in sediment core GIK14807-2. 60 records from Planktic foraminifera abundance of Hole 19-192. 24 records from New genera, species and records of Doryctinae (Hymenoptera: Braconidae) from Brazil. 700 records from Computarización de la colección de Salpas (Clase Thaliacea, Orden Salpida) del Pacífico mexicano y mar Caribe mexicano. 3 records from Ctenosciara alexanderkoenigi sp. n. (Diptera: Sciaridae), an exotic invader in Germany?. 43420 records from Plant Diversity and Distribution on the Continental Cameroon Mountains. 2 records from Agence_MTDA_2017_12_18. 3 records from Redescriptions of two closely related East Asian flatfish species of the genus Pleuronichthys. 3673 records from Diversité des espèces invasives des zones classées et terroirs villageois du Benin (Afrique de l'Ouest).. 14 records from A new species of Argulus (Crustacea, Branchiura, Argulidae) from the skin of catfish, with new records of branchiurans from wild fish in the Brazilian Pantanal wetland. 10 records from Description of Limyra, new genus with a new species and the redescription of Cibyra pluriargenteus (Viette), from southeastern Brazil (Lepidoptera: Hepialidae). 118 records from Lebensraum Stadt und Park. 19718188 records from Norwegian Species Observation Service. 46 records from Tejidos de Anfibios y Aves, en estudios bióticos en el Complejo de Páramos Chingaza. 27 records from First description of the sexuals of Camponotus opaciventris Mayr, 1879 (Hymenoptera, Formicidae), with notes on distribution in Western Himalaya. 126392 records from Manscape. 134 records from Total foraminifera counts of multinet POS247/2_MSN1381. 8 records from Distribution of meiobenthos in sediment core M23_133 of the northeastern Atlantic (Table 1). 14 records from Description of a new species of Euptychia Hübner, 1818 (Lepidoptera: Nymphalidae: Satyrinae) from the western Andes. 8567 records from Fishes in MZNA-VERT: populations affected by the Itoiz dam in the Irati river (Spain).. 68 records from Total foraminifera counts of multinet M21/4_MSN696. 17 records from New species and new records of ground spiders (Araneae: Gnaphosidae) from Cyprus. 11 records from Oberservation of birds at station PS14/145 along 49° West. 3257 records from fundiv france database. 68 records from A taxonomic review of the Indian species of the genus Eumenes Latreille (Hymenoptera: Vespidae: Eumeninae). 17 records from Dinoflagellate cysts of sediment core IOW211660-6. 497 records from Données naturalistes de Guilène PROCIDA. 26 records from Nanoplankton abundance at station GeoB2021-3. 1873 records from Herbarium BSG Bryophyta. 908 records from Megaloptera (Insecta: Neuropterida) de México. 6 records from Agroeca dentigera and Entelecara omissa (Araneae: Liocranidae, Linyphiidae), found in Sweden. 6 records from Range table from planktonic foraminifers in ODP Hole 141-862C. 6207 records from SDSM Invertebrate Collections. 5 records from Two new species of the millipede genus Glyphiulus Gervais, 1847 from Southwest China (Diplopoda: Spirostreptida: Cambalopsidae). 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 1778 records from Données naturalistes de Thomas LEBARD. 176 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 54 records from Heuschrecken_Raw1. 62108 records from Frost Entomological Museum. 85 records from The matchstick grasshopper genus Warramaba (Morabidae: Morabinae): a description of four new species and a photographic guide to the group. 1728 records from Saproxylic Beetles of the Tatra Mts.. 209 records from Estudio de la distribución geográfica de Peromyscus ochraventer y análisis de su variabilidad cromosómica. 3 records from New species of Rhorus Förster, 1869 (Hymenoptera: Ichneumonidae: Ctenopelmatinae) from South Korea. 3 records from The Neotropical species of Atractodes (Hymenoptera, Ichneumonidae, Cryptinae), II: the A. pleuripunctatus species-group. 593 records from Leicestershire Gastropod Records. 521 records from Range table from benthic foraminifers in ODP Hole 144-873A. 3130 records from Range table from benthic foraminifers in ODP Hole 154-926A. 23 records from (Table 4) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704B. 9543 records from Wader survey on Uist in 2007. 1 records from A new species of Macrocentrus (Hymenoptera: Braconidae) parasitizing larva of Dioryctria pryeri (Lepidoptera: Pyralidae). 6068 records from Les Poaceae, les Fabaceae, les Euphorbiaceae, les Caesalpiniaceae, les Cyperaceae, les Mimosaceae, les Hippocrateaeceae, les Lamiaceae, les Dioscoreaceae, les Ebenaceae et quelque 28 autres autres familles de l'herbier du Centre National de Floristique, en Côte d'Ivoire.. 525 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE275. 5008 records from The Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 60 records from Review of the tribe Helconini Foerster s. s. from China, with the description of 18 new species. 204 records from Dinoflagellate cysts of ODP Hole 189-1171D. 256 records from City of Edinburgh Natural Heritage Service - Bonaly Bird Survey. 38 records from Range table from planktonic foraminifers in ODP Hole 141-861B. 123 records from Range table from planktonic foraminifers in ODP Hole 167-1019C. 1374 records from Herbier du muséum Henri-Lecoq de Clermont-Ferrand - Apiaceae et Polygonaceae. 775 records from Sistema de apoyo a la toma de decisiones para la reforestación rural en México. 857 records from MEL: Marine cladocera collected from St. Margarets Bay between May to November, 1967-1969. 16881 records from Catalogue of Afrotropical Bees. 864 records from Phytoplankton abundance in surface water in November 1997, Ilo, Peru. 2200 records from Carabidae of the Tatra Mts.. 26 records from FND "Weißer Berg" Leißling. 10 records from Ballomma, a new Afrotropical genus in the Cryptothelinae (Araneae, Zodariidae): eyes on the run. 30 records from Riekdahler Wiesen. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 651 records from Groupe_Lamo_Naturae_2017_12_18. 399 records from Freshwater Shad Monitoring Data. 188 records from Modelación de la distribución geográfica de las especies del género Abies presentes en México. 5718 records from Colección Zoológica de la Universidad del Tolima (CZUT) - Lepidópteros. 214 records from NSG Haunestausee, Hauneteiche. 7678 records from RNF - Données de l'association ASTERS. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 1532 records from (Appendix B) Percentages, total flux and fragmentation index of planktic foraminifera for core T89-40, Walvis Ridge (SE Atlantic). 12 records from Clarification of Einfeldia Kieffer, 1922 (Diptera: Chironomidae) with E. australiensis (Freeman, 1961), comb. n. based on immature stages. 143 records from Planktic foraminifera counts at CTD station PS55/025. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 1156 records from Colección Entomológica de la Universidad Tecnológica del Chocó. 101 records from Rund ums Schulgelände. 12 records from Colección de Exhibición de Fósiles del Museo de Ciencias de la Universidad El Bosque. 4 records from The presence of the family Anostostomatidae (Orthoptera: Ensifera) in Argentina. 2 records from Discovery of Neopanorpa chillcotti Byers (Mecoptera: Panorpidae) from Tibet, China, with discussion of its generic status. 93 records from Südwestlich der Parkwiesen. 13 records from Microzooplankton abundance and biomass at station NBP97-08-33-5. 9799 records from Programa Integral de Protección de tortugas marinas. Temporadas 2007 a 2012. 3594 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 13 records from Nannofossil abundance of Hole 1-7. 14304 records from Conventions d’étude sur la biodiversité française – Partenariats du SPN. 12 records from Two new species of Huascaromusca Townsend from Colombia, and a new combination for Giovanella carvalhoi (Diptera: Mesembrinellidae). 3 records from Two new synonymies in the genus Lispe (Diptera: Muscidae). 35 records from Specimens from India at the Natural History Museum at the University of Oslo (NHM-UiO). 3313 records from Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 12 records from The genera Allophrys Förster and Aneuclis Förster (Hymenoptera: Ichneumonidae: Tersilochinae) of Vietnam. 57 records from A systematic revision of Charissa, subgenus Pterygnophos Wehrli, 1951, with description of a new species (Lepidoptera: Geometridae). 4 records from Two new species of Tomocerus ocreatus complex (Collembola, Tomoceridae) from Nanjing, China. 196 records from (Table 2) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 30-289. 511 records from Aves de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 7 records from Revision of the genus Palmanura Cassagnau, 1983 (Collembola: Neanuridae: Neanurinae: Sensillanurini). 5 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 281 records from Calcareous dinoflagellate cysts of multicorer M51/3_569-3, grain fraction > 20µm. 1728 records from (Table 3) Benthic foraminifera in early-middle Miocene sediments of DSDP Site 89-586. 17298 records from Upper Murrumbidgee Waterwatch. 704 records from Flora vascular y endemismos de las partes altas de varios macizos montañosos de Querétaro y norte de Michoacán-1ra Fase. 4 records from Revision of the polytypic electric fish Gymnotus carapo (Gymnotiformes, Teleostei), with descriptions of seven subspecies. 25 records from Inventario de Anfibios y Reptiles Mámbita. 771540 records from TAXA - Flore et habitats naturels de Franche-Comté. 780 records from Comportamiento espacio-temporal de la densidad fitoplanctónica en el año 2015 Magdalena, Colombia. 22144 records from Données Ongulés et Lagomorphes d'Alsace transmises par le GEPMA. 122031 records from BLS Lichen Database: Wales 1650-2016. 40 records from ZUEC-NEM - Coleção de Nemertea do Museu de Zoologia da UNICAMP. 1443 records from Trap data GBN3, 3921 m. 83 records from Aprovechamiento de venado cola blanca (Odocoileus virginianus) como estrategia para conservar áreas forestadas en la zona maya: Reserva Ría Lagartos, Yucatán. 6625 records from Lista florística preliminar de Tamaulipas. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-015. 44 records from Taxonomic notes and faunistic data on the Muscidae (Diptera) of the Altai Mountains (Russia). 87 records from (Table 3) Meiofauna abundance in surface sediments of Cape Lookout. 48 records from Foraminifera species abundances from tow TT007_9-MOC18. 12 records from Microzooplankton abundance and biomass at station NBP97-03-11-1. 114 records from Birdrace-Finkenspötter-München. 69 records from Phytoplankton abundance at station Casma_2003-03-27_1, Casma, Peru. 404 records from Planktic foraminifera counts of sediment core V22-26. 128 records from Total foraminifera counts of multinet POS231/3_MSN1336. 71 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-9. 575 records from (Table 7) Distribution of Maestrichtian to late Campanian nannofossils in ODP Hole 108-661A. 65 records from Schulhof A.-Lindgren-Schule (Elmshorn). 5314 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 221 records from Mangfalltal. 59612 records from African Plants - a photo guide. 339 records from Inventory of the free-living marine nematode specie from el Bibane Lagoon (Tunisia). 1 records from A new species of Nanophyllium Redtenbacher, 1906 from the northern coast of New Guinea (Phasmida, Phylliidae). 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 36 records from Nanno
Keywords: GBIF; biodiversity; species occurrences